Organic / inorganic hybrid membrane composite body, gas separation and / or concentration method, gas separation membrane module, and method for producing organic / inorganic hybrid membrane composite body
By controlling the ratio of surface roughness and film thickness in the organic-inorganic hybrid membrane and using high gas selectivity inorganic fillers, the problem of insufficient gas permeability and separation performance in the prior art is solved, and efficient gas separation and permeability is achieved.
Patent Information
- Application Number
- JP2024168645
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
In the prior art, when the organic-inorganic hybrid film increases the proportion of inorganic fillers, voids are easily formed, resulting in a degradation of gas separation performance and insufficient gas permeability of the film.
The ratio of surface roughness and film thickness in the organic-inorganic hybrid membrane is controlled to reach 0.050 or above, and inorganic fillers with high gas selectivity, such as zeolites and MOFs, are used to improve the gas permeability and separation performance of the membrane.
The high gas permeability and separation performance of the organic-inorganic hybrid film are achieved, avoiding the formation of voids and improving the overall performance of the film.
Smart Images

Figure 2025059102000006 
Figure 2025059102000007 
Figure 2025059102000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic-inorganic hybrid membrane composite, a gas separation and / or concentration method, a gas separation membrane module, and a method for producing an organic-inorganic hybrid membrane composite. [Background technology]
[0002] Gas separation and purification methods include membrane separation, adsorption separation, absorption separation, and cryogenic separation. Membrane separation is a method that uses pressure as a driving force to separate gases by the difference in speed of the gases that permeate the membrane. Since there is almost no phase change during the gas separation, it consumes less energy than other gas separation and purification methods. In recent years, there has been a demand to reduce greenhouse gases due to global climate change, and membrane separation, which consumes less energy, has attracted attention as an alternative to conventional separation methods and as a means of separating and recovering greenhouse gases.
[0003] Membranes for gas separation include polymer membranes that have been proposed since the 1970s, zeolite membranes made on ceramic supports, and organic-inorganic hybrid membranes called Mixed Matrix Membranes (MMMs), which are polymer membranes with inorganic fillers.
[0004] For example, MMMs, or organic-inorganic hybrid membranes, which are made by adding inorganic fillers such as zeolite with gas separation ability to a matrix resin, have attracted attention as a membrane that overcomes the drawbacks of both polymer membranes and inorganic membranes and combines their respective advantages (Non-Patent Document 1).
[0005] In an organic-inorganic hybrid membrane, it is believed that the more inorganic filler with higher separation and permeation performance than the matrix resin is mixed, the more gas separation performance close to that of the inorganic filler is shown. However, in reality, when the ratio of inorganic filler such as zeolite exceeds a certain level, voids are generated between the matrix resin and the inorganic filler, and gas passes through the voids, and the separation performance of the inorganic filler is not used, resulting in a decrease in performance (Non-Patent Document 1). In order to suppress the generation of voids between the inorganic filler and the matrix resin, many attempts have been made to modify the inorganic filler and improve its affinity with the matrix resin, but the effect is limited.
[0006] On the other hand, one of the causes of voids that occur between the matrix resin and the inorganic filler in an organic-inorganic hybrid film is the stress applied to the interface during film formation (Non-Patent Document 2). [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Progress in Materials Science 102 (2019) 222-295. [Non-Patent Document 2] Journal of Molecular Structure 739 (2005) 87-98. Summary of the Invention [Problem to be solved by the invention]
[0008] However, from the viewpoint of further improving gas permeance, there is room for improvement in conventional organic-inorganic hybrid membranes. The present invention has been made in view of such circumstances, and an object of the present invention is to provide a new organic-inorganic hybrid membrane composite having excellent permeance, and a related technique thereof. [Means for solving the problem]
[0009] As a result of extensive research aimed at solving the above problems, the inventors have discovered that in an organic-inorganic hybrid membrane containing a matrix resin and an inorganic filler having gas selectivity, by setting the ratio of the arithmetic mean roughness of the organic-inorganic hybrid membrane surface to the film thickness of the separation-related layer to be 0.050 or more, an organic-inorganic hybrid membrane composite having excellent permeance can be obtained, and have arrived at the present invention.
[0010] That is, the gist of the present invention resides in the following [1] to [6]. [1] An organic-inorganic hybrid membrane composite comprising a porous support layer and a separation-related layer formed on the porous support layer, the separation-related layer comprising an organic-inorganic hybrid membrane comprising a matrix resin and an inorganic filler having gas selectivity, and wherein the ratio of the arithmetic mean roughness of the surface of the organic-inorganic hybrid membrane composite to the film thickness of the separation-related layer is 0.050 or more. [2] The organic-inorganic hybrid membrane composite described in [1], wherein the maximum value of the ratio of the maximum length of the continuous inorganic filler to the thickness of the separation-related layer of the organic-inorganic hybrid membrane composite is 20% or more. [3] The organic-inorganic hybrid membrane composite according to [1] or [2], wherein the inorganic filler has at least two peaks in particle size distribution, comprises a first inorganic filler and a second inorganic filler having an average particle diameter smaller than that of the first inorganic filler, and the average particle diameter of the first inorganic filler is 1 μm or more. [4] A method for performing at least one of gas separation and gas concentration, using the organic-inorganic hybrid membrane composite according to any one of [1] to [3]. [5] A gas separation membrane module comprising the organic-inorganic hybrid membrane composite according to any one of [1] to [3]. [6] A method for producing an organic-inorganic hybrid membrane composite according to any one of [1] to [3], a casting step of applying a dispersion liquid containing at least one of a precursor and an intermediate of a matrix resin and an inorganic filler having gas selectivity onto the porous support layer; and a curing step of curing at least one of the precursor and the intermediate of the matrix resin to form the organic-inorganic hybrid film on the porous support layer. A method for producing an organic-inorganic hybrid membrane composite. Effect of the Invention
[0011] According to the present invention, there is provided a new organic-inorganic hybrid membrane composite having excellent permeance, and a related technique thereof. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram of an apparatus used for gas separation in the examples. [Diagram 2] FIG. 2 is a schematic diagram of an apparatus used in a mixed gas permeation separation test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following describes the embodiment of the present invention in more detail, but the following description of the components is an example of the embodiment of the present invention, and the present invention is not limited to these contents, and can be implemented in various modifications within the scope of the gist. In this specification, rubber and rubber are synonymous. In addition, the measuring devices, detectors, and software described in this specification may be replaced with other models and / or versions that are capable of equivalent measurement and processing.
[0014] <First aspect> Hereinafter, as a first aspect of the present invention, a new organic-inorganic hybrid membrane composite having excellent permeance and related techniques will be described.
[0015] <Organic-inorganic hybrid membrane composite> An organic-inorganic hybrid membrane composite according to one embodiment of the present invention comprises a porous support layer and a separation-related layer formed on the porous support layer, the separation-related layer comprising an organic-inorganic hybrid membrane, the organic-inorganic hybrid membrane comprising a matrix resin and an inorganic filler having gas selectivity, and the ratio of the arithmetic mean roughness of the surface of the organic-inorganic hybrid membrane composite to the film thickness of the separation-related layer is 0.050 or more.
[0016] In the present invention, the organic-inorganic hybrid membrane refers to a gas separation layer, and does not include a support layer, an underlayer, a protective layer, and the like.
[0017] The organic-inorganic hybrid membrane according to one embodiment of the present invention may be used as it is as a free-standing membrane without a support layer, or may be used in the form of a support membrane by forming the organic-inorganic hybrid membrane on an inorganic porous support layer or a porous support layer made of an organic polymer or an inorganic polymer. Examples of the porous support layer made of an organic polymer or an inorganic polymer include a porous organic film such as a porous membrane filter and a resin hollow fiber membrane.
[0018] The organic-inorganic hybrid membrane of the present invention may be formed on a porous support layer. An underlayer may be present between the porous support layer and the organic-inorganic hybrid membrane, or a protective layer may be present on the surface of the organic-inorganic hybrid membrane. The porous support layer and the organic-inorganic hybrid membrane formed on the porous support layer, as well as the underlayer and protective layer, if any, are collectively referred to as an organic-inorganic hybrid membrane composite.
[0019] [Matrix resin] The matrix resin in the present invention is a polymer compound, and refers to the portion of the organic-inorganic hybrid membrane other than the inorganic filler having gas selectivity.
[0020] The polymer compound constituting the matrix resin may be a thermoplastic resin or a resin obtained by a curing reaction and / or a crosslinking reaction. The polymer compound may be obtained by polymerizing and / or crosslinking a precursor. The polymer compound may also be obtained by polymerizing and / or crosslinking a part of the reactive groups of the precursor to obtain an intermediate, and then further polymerizing and / or crosslinking the reactive groups of the intermediate to obtain the polymer compound.
[0021] The precursor may be a monomer, oligomer, or polymer that is polymerized to form a polymer compound. The matrix resin may contain a residue of the precursor of the matrix resin, a surface treatment agent for the inorganic filler, a dispersant, a crosslinking agent, a catalyst for the polymerization reaction, a reaction control agent, and / or residues of these after the reaction.
[0022] When no precursor is used, a polymer compound in the form of pellets, sheets, granules, or powder can be used after being dissolved or melted in a solvent to give it fluidity.
[0023] The polymer compound contained in the matrix resin may be used alone or in combination of two or more kinds.
[0024] The glass transition temperature (Tg) of the matrix resin is not particularly limited, and is, for example, usually 15°C or less, preferably 0°C or less, more preferably -20°C or less, even more preferably -50°C or less, particularly preferably -70°C or less, and most preferably -100°C or less. When Tg is below the upper limit, even if the content of inorganic filler in the organic-inorganic hybrid membrane is increased, no gaps are generated between the inorganic filler and the matrix resin because the matrix resin has flexibility at the operating temperature, and sufficient gas separation performance tends to be exhibited. Furthermore, when Tg is below the upper limit, it becomes possible to highly fill the inorganic filler without generating gaps between the matrix resin and the inorganic filler, and a membrane exhibiting sufficient permeation and separation performance can be obtained. In addition, when Tg is equal to or lower than the upper limit, the flexibility of the matrix resin can absorb the distortion at the interface between the matrix resin and the inorganic filler even when used under high pressure conditions or for a long period of time, and gaps tend not to occur. In addition, since the matrix resin has flexibility, when the membrane is processed into a shape such as a spiral and modularized, no gaps occur between the matrix resin and the inorganic filler, and the membrane performance tends to be good. In addition, the lower limit of Tg is not particularly limited, but is preferably -250°C or higher, and more preferably -200°C or higher. The method for measuring the glass transition temperature is in accordance with the method described in the examples.
[0025] The gas permeability of the matrix resin in the present invention is not particularly limited, and for example, the gas permeability coefficient of CO2 at 35°C is preferably 200 Barrer or more, more preferably 500 Barrer or more, even more preferably 1000 Barrer or more, particularly preferably 1500 Barrer or more, and most preferably 2000 Barrer or more.
[0026] When the gas permeability coefficient of CO2 at 35°C is equal to or greater than the lower limit, the gas permeability coefficient of the film made of the matrix resin alone is sufficiently large, and the gas permeability coefficient of the organic-inorganic hybrid membrane composite having the organic-inorganic hybrid membrane can be increased. Note that the CO2 permeability coefficient at 35°C is measured under a differential pressure condition of 0.1 MPa for a film made of the matrix resin alone (hereinafter sometimes referred to as a resin film).
[0027] The separation coefficient, permeability coefficient, and permeability of the matrix resin are measured by preparing a membrane made of the matrix resin alone (hereinafter, sometimes referred to as a resin membrane) at 35°C and a differential pressure of 0.1 MPa using the same method as the measurement method for the organic-inorganic hybrid membrane according to one embodiment of the present invention.
[0028] The matrix resin or the polymer compound (polymer, polymeric material) contained in the matrix resin is preferably silicone rubber made of polyorganosiloxane such as polydimethylsiloxane (hereinafter sometimes referred to as PDMS), rubbers such as styrene-butadiene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, natural rubber, acrylic rubber, ethylene-vinyl oxide rubber, polyolefin such as poly(4-methyl-1-pentyne), more preferably silicone rubber made of polyorganosiloxane such as PDMS, rubbers such as styrene-butadiene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, natural rubber, acrylic rubber, ethylene-vinyl oxide rubber, and particularly preferably silicone rubber made of polyorganosiloxane such as PDMS. By forming an organic-inorganic hybrid membrane on a porous support layer using these resins, an organic-inorganic hybrid membrane composite with excellent gas permeability and separation performance can be obtained.
[0029] The silicone rubber that is preferable as the matrix resin or the polymer compound contained in the matrix resin is not particularly limited, but is preferably a polyorganosiloxane having a siloxane skeleton represented by the following general formula (1), or a commercially available silicone rubber precursor that is used as a precursor of the matrix resin and cured by a crosslinking reaction. Examples of commercially available silicone rubber precursors include SILPOT (registered trademark) 184 Silicone Elastomer Base (manufactured by Dow Toray Co., Ltd.).
[0030] [ka] In general formula (1), n is an integer of 2 or more, and R1 and R2 may each have, in whole or in part, a hydrogen atom, an alkyl group such as a methyl group or an ethyl group, a hydroxyl group, a cycloalkyl group such as a cyclohexyl group, a polyether group, an alkenyl group such as a vinyl group or an allyl group, an aryl group such as a phenyl group or a fluorenyl group, or a heteroalkyl group such as a fluoroalkyl group, a saturated or unsaturated alicyclic group containing a hetero element such as an oxiranyl group or an oxetanyl group, a condensation-reactive substituent such as an alkoxy group, a ketoxime group, an acetoxy group, or an aminoxy group, or a substituent such as an amino group, a carboxy group, a carbinol group, or an epoxy group. R1 and R2 are each independently reactive, and are preferably a hydrogen atom, a hydroxyl group, an alkenyl group such as a vinyl group or an allyl group, a condensation-reactive substituent such as an alkoxy group, a ketoxime group, an acetoxy group, or an aminoxy group, or a substituent such as an amino group, a carboxyl group, a carbinol group, or an epoxy group, and are particularly preferably a hydrogen atom, a hydroxyl group, or an alkenyl group such as a vinyl group or an allyl group. As for the form of substitution, R1 and R2 of the side chain may be substituted, both ends or one of both ends may be substituted, or both ends or one of both ends and the side chain may be substituted. R1 and R2 may be the same or different from each other, and only a part of R1 and R2 of the polyorganosiloxane may be substituted.
[0031] Examples of the substituents bonded to the Si atom at both ends or at one of both ends of the compound represented by general formula (1) include a hydrogen atom, an alkyl group such as a methyl group or an ethyl group, a hydroxy group, a cycloalkyl group such as a cyclohexyl group, a polyether group, an alkenyl group such as a vinyl group or an allyl group, an aryl group such as a phenyl group, a fluorenyl group, or a heteroalkyl group such as a fluoroalkyl group, a saturated or unsaturated alicyclic group containing a heteroatom such as an oxiranyl group or an oxetanyl group, a condensation-reactive substituent such as an alkoxy group, a ketoxime group, an acetoxy group, or an aminoxy group, an amino group, a carboxy group, a carbinol group, or an epoxy group. In terms of reactivity, a hydroxy group, an alkenyl group such as a vinyl group or an allyl group, an alkoxy group, a ketoxime group, an acetoxy group, or an aminoxy group, a condensation-reactive substituent such as a condensation-reactive substituent such as a ketoxime group, an acetoxy group, or an aminoxy group, an amino group, a carboxy group, a carbinol group, or an epoxy group is preferred, a hydrogen atom, a hydroxy group, an alkenyl group such as a vinyl group or an allyl group, or an alkoxy group is more preferred, and a hydrogen atom, a hydroxy group, a vinyl group, or an alkoxy group is particularly preferred.
[0032] As commercially available polyorganosiloxanes having hydroxy groups at the terminals of the general formula (1), poly(dimethylsiloxane), hydroxyl-terminated (viscosity 2550-3570 cSt), poly(dimethylsiloxane), hydroxyl-terminated (viscosity 18,000-22,000), and poly(dimethylsiloxane), hydroxyl-terminated (viscosity up to 50,000 cSt), all manufactured by Aldrich, are preferred, with poly(dimethylsiloxane), hydroxyl-terminated (viscosity 18,000-22,000) being particularly preferred.
[0033] In terms of polymerizing or condensing the polyorganosiloxane of general formula (1) through a crosslinking reaction to produce a silicone rubber, it is preferable that the polyorganosiloxane of general formula (1) has a crosslinkable group such as an alkenyl group including a vinyl group, a silicon-hydrogen bond, or a condensation-reactive substituent such as a hydroxyl group, an oxetanyl group, an alkoxy group, a ketoxime group, an acetoxy group, or an aminoxy group, and it is particularly preferable that the polyorganosiloxane has a silicon-hydrogen bond that can utilize an addition reaction, an alkenyl group, or a hydroxyl group that can utilize a condensation reaction.
[0034] In the present invention, the mechanism of the crosslinking reaction when crosslinking and curing polyorganosiloxane to obtain silicone rubber is not particularly limited, and conventionally known curing reactions using organic peroxides, condensation reactions, addition reactions, and curing reactions using ultraviolet light, radiation, and electron beam irradiation can be used. From the viewpoint of productivity, it is preferable to use a material that can stably mix inorganic fillers and store the inorganic fillers after mixing in the atmosphere, and in this respect, it is preferable to use a type that can be cured by addition reactions, condensation reactions, ultraviolet light, radiation, and electron beam irradiation, and it is particularly preferable to use addition reactions or condensation reactions because it is simple and does not require atmospheric control other than temperature and humidity.
[0035] [Crosslinking agent] In the present invention, the matrix resin may be obtained by reacting reactive substituents of polyorganosiloxane with each other to crosslink them, or the matrix resin may be obtained by using silanes having reactive substituents as shown in the following general formula (2) as a crosslinking agent for polyorganosiloxane.
[0036] [ka] (In the formula, R 1 is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms, R 2 are each independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms, and a is 3 or 4.
[0037] Here, in the general formula (2), R 1Examples of the unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 4 carbon atoms, represented by the following formula (1) include alkyl groups such as methyl group, ethyl group, propyl group, isopropyl group, butyl group, isobutyl group, sec-butyl group, tert-butyl group, pentyl group, hexyl group, heptyl group, octyl group, 2-ethylhexyl group, nonyl group, decyl group, and dodecyl group; cycloalkyl groups such as cyclopentyl group and cyclohexyl group; vinyl group, allyl group, propenyl group, isopropenyl group, Examples of such groups include alkenyl groups such as nyl, butenyl, pentenyl, and hexenyl; aryl groups such as phenyl, tolyl, xylyl, and α- and β-naphthyl; aralkyl groups such as benzyl, 2-phenylethyl, and 3-phenylpropyl; and groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as F, Cl, and Br, cyano groups, and methoxy groups, such as 3-chloropropyl, 3,3,3-trifluoropropyl, 2-cyanoethyl, and methoxymethyl groups. Among these, alkyl groups such as methyl and ethyl groups, alkenyl groups such as vinyl groups, and methoxymethyl groups in which one of the hydrogen atoms of a methyl group is substituted with a methoxy group are preferred in terms of not impairing the properties of the polyorganosiloxane, and ethyl and vinyl groups are particularly preferred.
[0038] In the general formula (2), R 2Examples of the unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 4 carbon atoms, represented by the following formula (1) include alkyl groups such as methyl group, ethyl group, propyl group, isopropyl group, butyl group, isobutyl group, sec-butyl group, tert-butyl group, pentyl group, hexyl group, heptyl group, octyl group, 2-ethylhexyl group, nonyl group, decyl group, and dodecyl group; cycloalkyl groups such as cyclopentyl group and cyclohexyl group; vinyl group, allyl group, propenyl group, isopropenyl group, Examples of such groups include alkenyl groups such as nyl, butenyl, pentenyl, and hexenyl; aryl groups such as phenyl, tolyl, xylyl, and α- and β-naphthyl; aralkyl groups such as benzyl, 2-phenylethyl, and 3-phenylpropyl; and groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as F, Cl, and Br, or cyano and methoxy groups, such as 3-chloropropyl, 3,3,3-trifluoropropyl, 2-cyanoethyl, and methoxymethyl. Among these, alkyl groups such as methyl and ethyl are particularly preferred in terms of their ease of availability and high reactivity.
[0039] Silanes having an ethoxy group as a crosslinkable substituent, i.e., silanes having R 2 Examples of silanes in which R is an ethyl group include tetraethyl orthosilicate, tetramethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, methyltris(methoxyethoxy)silane, vinyltris(methoxyethoxy)silane, methoxymethyltrimethoxysilane, methoxymethyltriethoxysilane, ethoxymethyltrimethoxysilane, ethoxymethyltriethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, and decyltrimethoxysilane. From the viewpoints of high reactivity and ease of handling, tetraethyl orthosilicate and tetramethoxysilane are preferred, and tetraethyl orthosilicate is particularly preferred.
[0040] [catalyst] In the present invention, when reacting polyorganosiloxane, a catalyst that promotes crosslinking reactions such as condensation reactions and addition reactions may be used. The type of catalyst is not particularly limited, and non-metallic organic catalysts or metal catalysts such as platinum and tin may be used as the catalyst.
[0041] The non-metallic organic catalyst is not particularly limited as long as it can be used as a known curing accelerator for condensation curing organopolysiloxane compositions. For example, phosphazene-containing compounds such as N,N,N',N',N'',N''-hexamethyl-N'''-(trimethylsilylmethyl)-phosphorimidic triamide, amine compounds or salts thereof such as hexylamine and dodecylamine phosphate, quaternary ammonium salts such as benzyltriethylammonium acetate, silanes and siloxanes containing guanidyl groups such as tetramethylguanidylpropyltrimethoxysilane, tetramethylguanidylpropylmethyldimethoxysilane, and tetramethylguanidylpropyltris(trimethylsiloxy)silane, are exemplified, but the non-metallic organic catalyst is not limited thereto.
[0042] The metal catalyst used in the curing reaction by condensation reaction is one or more selected from organic divalent tin compounds and organic tetravalent tin compounds. The organic divalent tin compounds are preferably divalent tin salts of carboxylic acids (salts of carboxylic acids and divalent tin (II)), and include dicarboxylate tin (II) compounds such as tin (II) 2-ethylhexanoate (also known as tin (II) octoate), tin (II) octanoate, and tin (II) neodecanoate. The organic tetravalent tin compounds include dialkyltin (IV) diester compounds such as dibutyltin (IV) diacetate, dibutyltin (IV) dilaurate, dibutyltin (IV) dioctoate, dioctyltin (IV) dilaurate, dioctyltin (IV) dineodecanoate, and dibutyltin (IV) diacetoacetate, and dialkyltin (IV) dialkoxy compounds such as di-n-butyl-dimethoxytin (IV). Among these, dialkyltin(IV) diester compounds are preferred, and in particular, easily available dioctyltin(IV) dilaurate and dioctyltin(IV) dineodecanoate are preferred, with dibutyltin(IV) dilaurate being particularly preferred.
[0043] Metal catalysts other than tin catalysts that can be used in the condensation reaction include, but are not limited to, those known as curing accelerators for condensation curing organopolysiloxane compositions. For example, titanium esters or titanium chelate compounds such as tetraisopropoxytitanium, tetra-n-butoxytitanium, tetrakis(2-ethylhexoxy)titanium, dipropoxybis(acetylacetonato)titanium, titanium isopropoxyoctylene glycol, and titanium diisopropoxybis(ethylacetoacetate), aluminum alcoholate compounds such as aluminum isopropylate and aluminum secondary butylate, aluminum alkyl acetate diisopropylate, and aluminum bisethylacetoacetate monoacetate. Examples of metal catalysts include aluminum chelate compounds such as cetylacetonate, zinc naphthenate, zinc stearate, zinc-2-ethyl octoate, iron-2-ethyl hexoate, cobalt-2-ethyl hexoate, manganese-2-ethyl hexoate, cobalt naphthenate, bismuth neodecanoate (III), bismuth 2-ethyl hexanoate (III), bismuth citrate (III), and organometallic compounds such as bismuth octylate, and lower fatty acid salts of alkali metals such as potassium acetate, sodium acetate, and lithium oxalate, but are not limited to these. Metal catalysts may be used alone or in combination.
[0044] As the metal catalyst, the platinum group metal catalyst is mainly used as a catalyst for the curing reaction by addition reaction.The type is not particularly limited, and examples thereof include platinum group metals such as platinum, palladium, rhodium, etc.; platinum compounds such as chloroplatinic acid, alcohol-modified chloroplatinic acid, coordination compounds of chloroplatinic acid with olefins, vinylsiloxane or acetylene compounds, platinum group metal compounds such as tetrakis(triphenylphosphine)palladium, chlorotris(triphenylphosphine)rhodium, etc.
[0045] The weight average molecular weight of the main polyorganosiloxane before curing, which is the matrix resin precursor or matrix resin intermediate to be mixed with the inorganic filler used in the present invention, measured by GPC (gel permeation chromatography) in terms of polystyrene is usually 5000 or more, preferably 10000 or more, more preferably 20000 or more, and even more preferably 25000 or more, and is usually 100000 or less. When the molecular weight of the main polyorganosiloxane before curing is within this range, the zeolite and the resin are easily mixed, and the film-forming property is also good, so that the inorganic filler filling ratio of the organic-inorganic hybrid film can be improved. In the present invention, the "main polyorganosiloxane" refers to the polyorganosiloxane that occupies the largest proportion of the polyorganosiloxanes contained in the matrix resin precursor or the matrix resin intermediate.
[0046] Examples of polyorganosiloxanes that can be suitably used in the present invention include SILPOT TM Examples of such silicones include ELASTOSIL RT601 manufactured by Wacker Asahi Kasei Silicones Co., Ltd., and poly(dimethylsiloxane), hydroxyl-terminated manufactured by Sigma-Aldrich Japan.
[0047] The method of GPC measurement is not particularly limited. The solvent used as the mobile phase can be selected from any solvent in which polyorganosiloxane before curing is soluble, such as toluene and chloroform. The column temperature is usually kept at 40°C. The detector is not particularly limited, and for example, an RI (differential refractive index) detector or a CAD (charged aerosol) detector can be used.
[0048] [Dispersant] In the present invention, when the inorganic filler is added when mixing the inorganic filler with one or more of the matrix resin, the matrix resin precursor, and the matrix resin intermediate, the viscosity increases and dispersion of the filler or film formation becomes difficult, a dispersant can be used. The dispersant may have the effect of improving the dispersibility and reducing the viscosity, as well as improving the handling property and leveling property.
[0049] The dispersant means a compound for uniformly dispersing the inorganic filler in the matrix resin. Examples of the dispersant include polysiloxane compounds and their salts, such as ethylhydrogenpolysiloxane, polymethoxysilane, dimethylpolysiloxane, or dimethicone PEG-7 succinate; silane compounds, such as methyldimethoxysilane, dimethyldimethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, dichlorophenylsilane, chlorotrimethylsilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltrichlorosilane, octadecyltrimethoxysilane, octadecyltrichlorosilane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, methyl ... Examples of the organic silicon compounds include ethoxylane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, hexamethyldisiloxane, 1,1,1,3,3,3-hexamethyldisilazane, and 3-carboxypropyltrimethyltrimethoxysilane; carboxylic acid compounds such as formic acid, acetic acid, butyric acid, lauric acid, stearic acid, oleic acid, and 6-hydroxyhexanoic acid; organic phosphorus compounds such as lauryl ether phosphoric acid or trioctylphosphine; amine compounds such as dimethylamine, tributylamine, trimethylamine, cyclohexylamine, ethylenediamine, and polyethyleneimine, carboxylic acid amine compounds, and phosphate amine compounds, as well as organic modified silicone resins and organic modified silicone oils as described in JP 2017-66364 A. The carboxylic acid amine compound refers to a compound having both functional groups of a carboxyl group and an amino group, and the phosphate amine compound refers to a compound having both functional groups of a phosphate group and an amino group.
[0050] Among them, organic modified silicone resin and / or organic modified silicone oil are preferred because they have affinity to both inorganic filler and matrix resin (especially silicone resin).The organic group of organic modified silicone resin and / or organic modified silicone oil includes epoxy group, alcohol group, carboxy group, acrylic group, allyl group, vinyl group, methacrylic group, thiol group, amino group, ether group, aralkyl group, alkyl group, etc.Among them, it is preferred to use at least one organic modified silicone resin and / or organic modified silicone oil modified with epoxy group, alcohol group, vinyl group or carboxy group, and more preferably to include at least organic modified silicone resin and / or organic modified silicone oil modified with epoxy group or vinyl group.
[0051] The organic modified silicone resin and / or the organic modified silicone oil as described above have an organic group with moderate polarity, and therefore are easily adsorbed to inorganic fillers. Therefore, by including the organic modified silicone resin and / or the organic modified silicone oil as described above in the composition, they are easily present on the inorganic filler surface, and the structural viscosity caused by the inorganic filler can be destroyed. Specifically, the silicone part, which is the -Si-O-Si- bond part of the organic modified silicone resin and / or the organic modified silicone oil, contacts the low polarity part of the inorganic filler, and the organic group part contacts the polar part of the inorganic filler, and thus functions as a surfactant that eliminates the phase separation structure in the resin composition, and the dispersibility of the inorganic filler is improved, thereby improving the filling rate of the inorganic filler in the organic-inorganic hybrid film.
[0052] The ratio of the organic modified silicone resin and / or the organic modified silicone oil is usually 1% or more, preferably 3% or more, more preferably 5% or more, and usually 50% or less, preferably 30% or less, more preferably 10% or less, based on the mass of the organic-inorganic hybrid film. When the ratio of the organic modified silicone resin and / or the organic modified silicone oil is within the above range, the viscosity of the organic-inorganic hybrid film during film formation can be reduced. In addition, the dispersibility of the inorganic filler can be improved, and the long-term stability of the organic-inorganic hybrid film can be ensured. In addition, when the ratio of the organic modified silicone resin and / or the organic modified silicone oil is below the upper limit, the ratio of the matrix resin increases, and the obtained organic-inorganic hybrid film becomes stronger and tends to be less prone to defects.
[0053] [Inorganic filler] The inorganic filler having gas selectivity used in the present invention is an inorganic compound having gas selectivity due to molecular sieve effect and / or adsorption selectivity, such as passing some gases but not passing other gases or having a significantly low permeation rate. The inorganic filler may be used alone or in combination of two or more kinds. It may also be used in combination with an inorganic compound having no gas selectivity.
[0054] Specific examples of the gas-selective inorganic filler include zeolite, metal-organic framework (hereinafter sometimes referred to as MOF), and porous metal complex (hereinafter sometimes referred to as PCP). The gas-selective inorganic filler used in the present invention preferably contains one or more of zeolite, MOF, and PCP, and desirably contains at least zeolite.
[0055] MOFs for use in the present invention include, for example, metal-organic frameworks that contain zinc ions coordinated to triazolates and / or oxalates, as well as the zeolite-like imidazolate structure-8 (ZIF-8).
[0056] As inorganic compounds other than the inorganic filler having gas selectivity, silica, α-alumina, γ-alumina, zirconia, titania, yttria, silicon nitride, boron nitride, silicon carbide, etc. Adding these inorganic compounds in addition to the inorganic filler having gas selectivity may facilitate film formation or improve the physical properties of the organic-inorganic hybrid film other than gas permeability.
[0057] The inorganic filler used in the present invention preferably contains zeolite, and the zeolite has a framework density (hereinafter referred to as FD) in which all elements (T elements) other than oxygen constituting the framework are assumed to be Si. Si ), but usually 18.0T / 1000Å 3 or less, preferably 17.0 or less, more preferably 16.0 or less, and even more preferably 15.8T / 1000Å or less 3 Less than 15.5T / 1000Å, more preferably 3 Less than 15.3T / 1000Å, more preferably 15.3T / 1000Å 3 Below, particularly preferably 15.2T / 1000Å 3 Below, most preferably 15.1T / 1000Å 3 Less than or equal to 10T / 1000Å 3 More than 11T / 1000Å, preferably 11T / 1000Å 3 More preferably, 12T / 1000Å or more 3 That's all.
[0058] Here, the framework density (T / 1000Å) when all T elements are Si is 3 ) is the 1000Å diameter of zeolite. 3 This means the number of elements other than oxygen that make up the framework, i.e., Si, per unit area, and this value is determined by the structure of the zeolite. The relationship between framework density and zeolite structure is shown in the Zeolite Structure Database (https: / / asia.iza-structure.org / IZA-SC / ftc_table.php). Therefore, FD Si The smaller the value, the more space there is in the zeolite structure.
[0059] When zeolite is used to make an organic-inorganic hybrid membrane, the matrix resin may clog the surface or inside of the zeolite pores. Si When FD is within the above range, the zeolite has a large amount of internal space, so that even if some of the space is blocked, a gas flow path can be secured, and the effect of mixing the zeolite is easily exerted effectively, and the organic-inorganic hybrid membrane composite tends to exhibit a high gas permeability coefficient and high separation performance. Si When the molecular weight is within the above range, the skeleton of the zeolite has sufficient strength, so that the zeolite tends to be stable and not easily broken, which is preferable.
[0060] The structures of the zeolites preferred in the present invention are generally AEI, AFR, AFS, AFT, AFV, AFX, AFY, AST, AVL, * BEA, BEC, BOZ, BPH, CHA, -CLO, CON, DFO, EAB, EMT, ETR, * -EWT, FAU, GME, -IFT, -IFU, IFW, IRN, IRR, -IRY, ISV, ITE, * -ITN, ITT, -ITV, IWR, IWS, IWV, JSR, JST, KFI, LEV, LTA, MEI, MWW, NPO, NPT, OBW, OSO, PAU, POS, PUN, PWN, RHO, RWY, SAO, SAS, SAV, SBE, SBS, SBT, SFO, SFW, SOV, * -SVY, -SYT, THO, TSC, UFI, USI, UTL, VFI, preferably AEI, AFR, AFS, AFT, AFV, AFX, AFY, AST, AVL, * BEA, BEC, BOZ, BPH, CHA, -CLO, CON, DFO, EMT, ETR, * -EWT, FAU, GME, -IFT, -IFU, IFW, IRN, IRR, -IRY, ISV, ITE, ITT, -ITV, IWR, IWS, IWV, JSR, JST, K FI, LTA, MEI, NPT, OBW, OSO, POS, PUN, PWN, RHO, RWY, SAO, SAS, SAV, SBE, SBS, SBT, SFO, SFW, SOV, *-SVY, -SYT, THO, TSC, UFI, UTL, VFI, more preferably AEI, AFR, AFS, AFT, AFX, AFY, * BEA, BEC, BOZ, BPH, CHA, -CLO, DFO, EMT, ETR, * -EWT, FAU, GME, -IFT, -IFU, IRN, IRR, -IRY, ISV, ITT, -ITV, IWS, IWV, JSR, JST, KFI, LTA, MEI, NPT, OBW, OSO, POS, PUN, RHO, RWY, SA O, SAS, SAV, SBE, SBS, SBT, SFO, SFW, SOV, -SYT, TSC, UFI, VFI, more preferably AEI, AFS, AFT, AFX, AFY, BEC, BOZ, BPH, CHA, -CLO, DFO, EMT, * -EWT, FAU, GME, -IFT, -IFU, IRR, -IRY, ISV, ITT, IWS, IWV, JSR, JST, KFI, LTA, MEI, NPT, OBW, OSO, PUN, RHO, RWY, SAO, SAS, SAV, SBE, SBS, SBT, SFW, SOV, -SYT, TSC, VFI, more preferably AEI, AFX, CHA, EMT, FAU, GME, KFI, LTA, MEI, NPT, RHO, VFI, particularly preferably AEI, AFX, CHA, FAU, and most preferably CHA. When the zeolite has the above structure, there is a large amount of space inside the zeolite, so that the matrix resin does not completely block the pores, and an organic-inorganic hybrid membrane composite having an organic-inorganic hybrid membrane exhibiting high permeation and separation performance can be obtained.
[0061] The main zeolite used in the present invention is not particularly limited, but is preferably a zeolite having 12 or less oxygen rings, more preferably a zeolite having 10 or less oxygen rings, and most preferably a zeolite having 8 or less oxygen rings. In addition, usually, a zeolite having 6 or more oxygen rings is preferred, and more preferably a zeolite having 8 or more oxygen rings. In the present invention, the "main zeolite" refers to the zeolite that occupies the largest proportion of the zeolites contained in the inorganic filler.
[0062] The value of n in the zeolite having n-membered oxygen rings refers to the zeolite with the largest number of oxygen atoms among the pores composed of oxygen and T elements (elements other than oxygen that compose the framework) that form the zeolite framework. For example, when pores with 12-membered oxygen rings and 8-membered oxygen rings exist, such as in MOR-type zeolites, the zeolite is considered to have 12-membered oxygen rings.
[0063] Zeolites with 12 or fewer oxygen ring members include AEI, AFR, AFS, AFT, AFV, AFX, AFY, AST, AVL, * BEA, BEC, BOZ, BPH, CHA, CON, DFO, EAB, EMT, FAU, GME, IFW, IRN, ISV, ITE, * -ITN, IWR, IWS, IWV, JSR, JST, KFI, LEV, LTA, MEI, MWW, NPO, NPT, OBW, PAU, POS, PUN, PWN, RHO, RWY, SAO, SAS, SAV, SBE, SBS, SBT, SFO, SFW, SOV, THO, TSC, UFI, and USI are listed. Zeolites with 10 or fewer oxygen rings include AEI, AFT, AFV, AFX, AST, AVL, BOZ, CHA, EAB, IFW, IRN, ITE, JST, KFI, LEV, LTA, MWW, NPT, OBW, PAU, PWN, RHO, SAS, SAV, SFW, THO, TSC, and UFI. Zeolites with 8 or fewer oxygen ring members include AEI, AFT, AFV, AFX, AST, AVL, CHA, EAB, IRN, ITE, KFI, LEV, LTA, NPT, PAU, PWN, RHO, SAS, SAV, SFW, THO, TSC, and UFI.
[0064] The n-membered oxygen ring structure determines the size of the zeolite pores. When the n-membered oxygen ring structure is within the above-described range, the zeolite is likely to exhibit high gas separation performance, and when made into an organic-inorganic hybrid membrane, the effect of increasing the gas separation performance beyond that of the matrix resin is likely to be obtained.
[0065] Main zeolites used in the present invention include aluminosilicates, aluminophosphates (AlPO), silicoaluminophosphates (SAPO), metallo-aluminophosphates (MeAPO), and metallo-silicoaluminophosphates (MeAPSO). Of these, aluminosilicates and silicoaluminophosphates (SAPO) are preferred, and aluminosilicates are particularly preferred from the viewpoint of the durability of the zeolite.
[0066] The SiO2 / Al2O3 molar ratio of the aluminosilicate is usually 5 or more, preferably 6 or more, more preferably 7 or more, even more preferably 8 or more, even more preferably 10 or more, even more preferably 12 or more, particularly preferably 15 or more, and most preferably 20 or more. The upper limit is usually 2000 or less, preferably 1000 or less, more preferably 500 or less, even more preferably 100 or less, and particularly preferably 50 or less. The SiO2 / Al2O3 molar ratio of the aluminosilicate is FD Si is within the above range, the lower limit may be even lower, and is usually 0.5 or more, preferably 1 or more, more preferably 3 or more, more preferably 8 or more, more preferably 10 or more, more preferably 12 or more, particularly preferably 15 or more, and most preferably 20 or more. The upper limit is usually 2000 or less, preferably 1000 or less, more preferably 500 or less, more preferably 100 or less, and particularly preferably 50 or less. When the SiO2 / Al2O3 molar ratio is within the above range, the durability of the zeolite is high, and the durability of the gas separation and permeation performance of the organic-inorganic hybrid membrane composite tends to be good. In addition, when the SiO2 / Al2O3 molar ratio is within the above range, the zeolite is not too hygroscopic, so that pretreatment before use of the organic-inorganic hybrid membrane composite is unnecessary or heating at a low temperature for a short time is sufficient, which is preferable. Furthermore, in the actual gas separation process, it is less affected by the moisture in the actual gas, so that in the gas separation process, the pretreatment of the gas introduced into the organic-inorganic hybrid membrane composite can be light, which is economical.
[0067] The SiO2 / Al2O3 molar ratio is determined by preparing a calibration curve in advance using ICP (inductively coupled plasma) analysis and X-ray fluorescence analysis (XRF), and then using XRF. Specifically, the procedure is as follows:
[0068] The zeolite sample was dissolved by heating in a hydrochloric acid solution, and the silicon atom and aluminum atom contents (mass%) were determined by ICP analysis. A calibration curve was then created between the fluorescent X-ray intensity of the analyzed element in the standard sample and the atomic concentration of the analyzed element. Using this calibration curve, the silicon atom and aluminum atom contents (mass%) in the zeolite sample were determined by XRF.
[0069] The average particle size of the inorganic filler used in the present invention is usually 0.05 μm or more, preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more, and is usually 20 μm or less, preferably 17 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, and particularly preferably 7 μm or less. When the average particle size of the inorganic filler is within this range, the inorganic filler has good dispersibility, making it easy to mix the inorganic filler with the matrix resin in any ratio, and a path through the inorganic filler is easily formed when the gas permeates, so that the effect of improving the separation and permeation performance by the inorganic filler is easily manifested, and it tends to be easy to obtain an organic-inorganic hybrid membrane composite with excellent separation and permeation performance.
[0070] The method for measuring the average particle size is specifically as follows.
[0071] [Method of measuring average particle size] The particle size of the inorganic filler used in the organic-inorganic hybrid film is determined by dispersing the synthesized powder thoroughly to prepare a sample, measuring the particle sizes of 30 randomly selected particles in an image taken with a scanning electron microscope, and taking the arithmetic mean of the measured particle sizes. For secondary particles formed by agglomeration of small crystal particles, this refers to the secondary particle size.
[0072] The particle diameter of the inorganic filler in the obtained organic-inorganic hybrid film is determined by photographing a cross-section of the organic-inorganic hybrid film obtained by freeze-fracturing the organic-inorganic hybrid film composite using a scanning electron microscope, measuring the particle diameters of 30 arbitrarily selected particles of the inorganic filler observed in the obtained cross-sectional image, and taking the arithmetic mean to determine the average particle diameter.
[0073] In either method, the particle size is defined as the diameter of a circle having an area equal to the projected area of the particle (equivalent circle diameter).
[0074] The inorganic filler used in the present invention may be a secondary particle formed by an aggregation of small crystal particles, or a primary particle in which crystal particles exist alone, so long as the particle size is within the above-mentioned range. However, primary particles are particularly preferred, since gaps called grain boundaries are unlikely to occur between the crystals, and defects called voids between the resin and the particles are unlikely to occur when the organic-inorganic hybrid membrane is formed, and the organic-inorganic hybrid membrane composite tends to exhibit a high separation factor.
[0075] In the present invention, when two types of inorganic fillers with different average particle sizes are used, the ratio of the average particle size of each is usually 1.5 or more, preferably 3 or more, more preferably 5 or more, and usually 100 or less, preferably 50 or less, more preferably 20 or less, and particularly preferably 15 or less, in terms of the value of the average particle size of the large particles / the average particle size of the small particles. When the particle size ratio is within this range, when the inorganic filler is mixed with the matrix resin, the space between the inorganic fillers is minimized, and the filling ratio of the inorganic filler can be improved. In addition, when three or more types of inorganic fillers with average particle sizes are used, it is preferable that two of them satisfy the particle size ratio described here.
[0076] Here, large particles refer to particles of the inorganic filler with the larger average particle diameter of two types of inorganic fillers with different average particle diameters, and small particles refer to particles of the inorganic filler with the smaller average particle diameter, and so on.
[0077] [Particle size distribution] The particle size distribution in the present invention is a volume-based particle size distribution. Although the method for determining the volume-based particle size distribution is not particularly limited, the laser diffraction / scattering method is suitable for inorganic fillers in a powder state before film formation. In the organic-inorganic hybrid membrane or organic-inorganic hybrid membrane composite after film formation, the particle size distribution of the inorganic filler contained in the organic-inorganic hybrid membrane and the separation-related layer can be determined by image analysis. That is, the cross section created by freeze fracture is observed with a scanning electron microscope, particles observed by the observation are selected, and image analysis is performed to determine the volume-based particle size distribution. The average particle size of the large particles and the small particles can be determined for each of the two types of inorganic fillers used according to the method for measuring the average particle size described below. When large and small particles are mixed, the inorganic filler powder used is well dispersed to prepare a sample, and the particle diameters of 30 or more particles selected at random are measured in an image taken with a scanning electron microscope, the volume-based particle size distribution obtained is converted to a number-based particle size distribution, and the average particle diameters of particles larger than the minimum value in the volume-based particle size distribution are calculated by taking the number-based arithmetic mean of particle diameters for particles larger than the minimum value and particles smaller than the minimum value. The average particle diameters of the large and small particles contained in the inorganic filler in the obtained organic-inorganic hybrid film can be calculated by photographing the cross section of the organic-inorganic hybrid film obtained by freeze fracture using a scanning electron microscope, measuring the particle diameters of 30 or more particles selected at random for the inorganic filler observed in the image of the cross section obtained, converting the volume-based particle size distribution obtained to a number-based particle size distribution, and taking the number-based arithmetic mean of particle diameters for particles larger than the minimum value and particles smaller than the minimum value. When there are three or more peaks, the average particle diameters are calculated by appropriately taking the arithmetic mean of particle diameters for particles between the minimum values on a number basis.
[0078] In this specification, the term "particle size" refers to the secondary particle size of secondary particles formed by agglomeration of small crystal particles, and the particle size is the diameter of a circle (equivalent circle diameter) having an area equal to the projected area of the particle in either method. The average particle size measured by the method for measuring the average particle size described below is also measured based on the particle size described here.
[0079] In the present invention, when two types of inorganic fillers with different average particle sizes (for example, a first inorganic filler and a second inorganic filler with an average particle size smaller than the first filler) are used, the inorganic filler contained in the organic-inorganic hybrid film has at least two peaks in particle size distribution. In the present invention, when the particle size distribution of the inorganic filler contained in the organic-inorganic hybrid film has at least two peaks, the peak (particle size at the peak top) of the first inorganic filler with a larger average particle size is usually between 0.5 μm or more, preferably 1 μm or more, and usually between 15 μm or less, preferably 10 μm or less, and more preferably between 7 μm or less, and the peak (particle size at the peak top) of the second inorganic filler with a smaller average particle size is usually between 0.1 μm or more, preferably 0.2 μm or more, and usually between 1 μm or less. By having a particle size distribution in these ranges, the filling rate of the inorganic filler in the organic-inorganic hybrid film can be improved. Thus, the inorganic filler's performance is fully exhibited, resulting in an organic-inorganic hybrid membrane with higher separation and permeation performance. In the present invention, when the particle size distribution of the inorganic filler contained in the organic-inorganic hybrid membrane composite has at least two peaks, when the particle size of the smaller peak is taken as 1, the particle size of the larger peak is usually 1.5 or more, preferably 2.0 or more, more preferably 5.0 or more, even more preferably 7.0 or more, and usually 100 or less, preferably 50 or less, even more preferably 20 or less, and particularly preferably 15 or less. When the particle size ratio is within this range, when the inorganic filler is mixed with the matrix resin, the space between the inorganic filler particles is minimized, and the filling ratio of the inorganic filler can be improved. In an embodiment in which the particle size distribution of the inorganic filler has two or more peaks, it is preferable that the relationship of the particle size ratio described here is satisfied for two of the peaks.
[0080] In the present invention, in an embodiment using two types of inorganic fillers with different average particle sizes, the preferred range of particle size is as follows. The average particle size of the first inorganic filler, which is a large particle, is usually 0.5 μm or more, preferably 1 μm or more, and is usually 15 μm or less, preferably 10 μm or less, more preferably 7 μm or less, and the average particle size of the small particle is usually 0.1 μm or more, preferably 0.2 μm or more, and is usually 1 μm or less. When the average particle sizes of the large and small particles of the inorganic filler are within this range, the dispersibility of the inorganic filler is good, it is easy to mix the inorganic filler with the matrix resin in any ratio, and a path through the inorganic filler is easily formed when the gas permeates, so the effect of improving the separation and permeation performance by the inorganic filler is easily manifested, and it is easy to obtain an organic-inorganic hybrid membrane with excellent separation and permeation performance.
[0081] In the present invention, in an embodiment using two kinds of inorganic fillers with different average particle sizes, when the average particle size of the smaller one is taken as 1, the average particle size of the larger one is usually 1.5 or more, preferably 2.0 or more, more preferably 5.0 or more, even more preferably 7.0 or more, and usually 100 or less, preferably 50 or less, even more preferably 20 or less, and particularly preferably 15 or less. When two kinds of inorganic fillers with different average particle sizes are used, when the average particle size of the larger one is within these ranges relative to the average particle size of the smaller one, the inorganic filler with the smaller average particle size can efficiently fill the particle gaps between the inorganic fillers with the larger average particle size, and the filling rate of the inorganic filler in the organic-inorganic hybrid membrane can be improved. Therefore, the performance of the inorganic filler is fully exhibited, resulting in an organic-inorganic hybrid membrane with higher separation and permeation performance.
[0082] In an embodiment in which two or more types of inorganic fillers having different average particle sizes are used, it is preferable that the average particle sizes of two of them satisfy the particle size ratio relationship described herein.
[0083] In the present invention, in an embodiment in which two kinds of inorganic fillers having different average particle sizes are used, the mass of the large particles is not particularly limited when the mass of the small particles is taken as 1, but is preferably 3 or more, more preferably 4 or more, and even more preferably 4.5 or more. Usually, it is preferably 10 or less, more preferably 8 or less, and more preferably 6 or less.
[0084] The mass ratio of large particles to small particles can be calculated from the peak area of the volume-based particle size distribution of the inorganic filler.
[0085] In the present invention, the ratio of the inorganic filler mass having gas selectivity to the total mass of the organic-inorganic hybrid membrane is usually 35% by mass or more, preferably 37% by mass or more, more preferably 42% by mass or more, even more preferably 48% by mass or more, even more preferably 52% by mass or more, even more preferably 57% by mass or more, particularly preferably 62% by mass or more, even more preferably 65% by mass or more, more preferably 70% by mass or more, even more preferably 75% by mass or more, and most preferably 80% by mass or more. The ratio is usually 99% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less. When the ratio of the inorganic filler mass is within this range, the organic-inorganic hybrid membrane composite is a composite that maintains flexibility and has excellent processability, and also tends to exhibit high separation and permeation performance.
[0086] The proportion of inorganic filler in the organic-inorganic hybrid film can be determined by selecting a normal analytical method according to the physical properties of the resin and inorganic filler. For example, the proportion of inorganic filler to the total mass of the organic-inorganic hybrid film can be determined by burning off all the resin parts using thermogravimetry (TG).
[0087] In the organic-inorganic hybrid film of silicone resin and inorganic filler, for example, a silicone resin decomposer is used to decompose the silicone resin in the organic-inorganic hybrid film, and the solid content is separated by filtration or centrifugation to obtain the mass of the inorganic filler, and the ratio to the total mass of the organic-inorganic hybrid film can be obtained. As the silicone resin decomposer, commercially available silicone resin decomposers such as methyl orthoformate and Dijesil NC manufactured by Ecosearch Co., Ltd., and silicone dissolving agents such as Silicone Cleaner manufactured by Nisshin Chemical Research Institute Co., Ltd. can be used.
[0088] In the present invention, when the organic-inorganic hybrid membrane also contains an inorganic filler that does not have gas selectivity, the ratio of the mass of the inorganic filler (the total mass of the inorganic filler having gas selectivity and the inorganic filler having no gas selectivity) to the total mass of the organic-inorganic hybrid membrane is not particularly limited, and is, for example, 35 mass% or more, preferably 37 mass% or more, more preferably 42 mass% or more, even more preferably 48 mass% or more, even more preferably 52 mass% or more, even more preferably 57 mass% or more, particularly preferably 62 mass% or more, even more preferably 65 mass% or more, more preferably 70 mass% or more, even more preferably 75 mass% or more, and most preferably 80 mass% or more. The ratio is usually 99 mass% or less, preferably 95 mass% or less, more preferably 90 mass% or less. When the mass ratio of the inorganic filler is in this range, the organic-inorganic hybrid membrane composite is a composite that maintains flexibility and has excellent processability, and tends to exhibit high separation and permeation performance.
[0089] In the present invention, the filling ratio of the zeolite in the organic-inorganic hybrid membrane is usually 20 vol% or more, more preferably 30 vol% or more, even more preferably 40 vol% or more, even more preferably 50 vol% or more, even more preferably 60 vol% or more, particularly preferably 65 vol% or more, and most preferably 70 vol% or more, as a volume fraction. The ratio is usually 99 vol% or less, preferably 95 vol% or less, more preferably 90 vol% or less, even more preferably 85 vol% or less, and particularly preferably 80 vol% or less. When the volume fraction of the zeolite is in this range relative to the volume of the organic-inorganic hybrid membrane, the organic-inorganic hybrid membrane composite tends to be a composite that maintains flexibility and has excellent processability, and also tends to exhibit high separation and permeation performance.
[0090] The volume fraction of zeolite in the organic-inorganic hybrid membrane can be determined by observing the cross section of the organic-inorganic hybrid membrane composite with a SEM (scanning electron microscope), calculating the area fractions of the inorganic filler, inorganic filler having gas selectivity, and zeolite for five or more fields of view from the cross section of the organic-inorganic hybrid membrane corresponding to the separation layer, which is not the support layer, underlayer, or protective layer, and taking the arithmetic average, which is the volume fraction of the inorganic filler, inorganic filler having gas selectivity, and zeolite in the organic-inorganic hybrid membrane. Since the inorganic filler, inorganic filler having gas selectivity, and zeolite can be considered to be uniformly dispersed on average in the organic-inorganic hybrid membrane, the area fraction can be considered to be equal to the volume fraction, since it is considered that the same area fraction as that of a part of the cross section is maintained on average in the depth direction of the cross section.
[0091] Inorganic fillers, inorganic fillers with gas selectivity, and zeolites can be distinguished from each other by their shapes in cross-sectional SEM observations and by composition analysis using SEM-EDX (scanning electron microscope-energy dispersive X-ray spectroscopy).
[0092] In the present invention, when zeolite and an inorganic filler other than zeolite are used in combination, the ratio of the mass of the inorganic filler other than zeolite to the mass of zeolite is usually 30% or less, preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less, and the lower limit is not particularly limited, but is usually 0.1% or more. When the mass% of the inorganic filler other than zeolite is within this range, the obtained organic-inorganic hybrid membrane composite is a composite that maintains flexibility and has excellent processability, and also tends to be a composite that exhibits high separation and permeation performance.
[0093] The shape of the inorganic filler used in the present invention is not particularly limited, but a particle shape of a sphere, cube, rectangular parallelepiped, or hexagonal column is preferable, and a sphere or cube is particularly preferable, and a sphere is most preferable. When the inorganic filler has such a shape, the loading amount of the inorganic filler can be increased, and an organic-inorganic hybrid membrane with high separation and permeability can be obtained.
[0094] The inorganic filler having the above-mentioned shape can be obtained by controlling the synthesis method, or by physically polishing the synthesized powder.
[0095] When the inorganic filler is spherical, the particles have high fluidity, which makes it possible to improve the particle packing rate, especially when the film is formed and cured under pressure.When the inorganic filler is cubic, the particles can be arranged well to reduce the gaps between the particles, which makes it possible to improve the packing rate of the inorganic filler in the organic-inorganic hybrid film.
[0096] The inorganic filler used in the present invention preferably has an average circularity coefficient of 0.80 or more, and particularly preferably 0.90 or more. The average circularity coefficient is usually 1.0 or less. When the average circularity coefficient is in this range, the particles have high fluidity, making it possible to improve the particle packing rate, and the packing rate can be improved particularly when the film is formed and cured under pressure. The circularity coefficient here is expressed as 4πS / L, where S is the area of a two-dimensional projection image of a particle of the inorganic filler used, and L is the circumferential length of the particle.2 When the particle is a perfect sphere, it is expressed as 1.0, and the closer the particle is to a perfect sphere, the larger the value becomes.
[0097] The method for calculating the average circularity coefficient is specifically as follows.
[0098] [Calculation method of average circularity coefficient] The average circularity coefficient of the inorganic filler used in the organic-inorganic hybrid film is determined by dispersing the synthesized powder thoroughly to prepare a sample, photographing it using a scanning electron microscope, calculating the circularity coefficient of 30 randomly selected particles, and taking the arithmetic average of the calculated values. For secondary particles formed by agglomeration of small crystal particles, the circularity coefficient of each secondary particle is calculated and the average value is taken.
[0099] The average circularity coefficient of the inorganic filler in the obtained organic-inorganic hybrid film and organic-inorganic hybrid film composite is determined by photographing the cross section of the organic-inorganic hybrid film obtained by freeze-fracturing using a scanning electron microscope, calculating the circularity coefficients of 30 arbitrarily selected particles of the inorganic filler visible in the cross section, and taking the arithmetic mean of these values.
[0100] In an embodiment in which the particle size distribution of the inorganic filler contained in the organic-inorganic hybrid membrane and the organic-inorganic hybrid membrane composite has at least two peaks, the average circularity coefficient is calculated in the same manner for particles larger than the minimum value of the particle size distribution and for particles smaller than the minimum value.
[0101] In addition, in an embodiment in which the particle size distribution of the inorganic filler contained in the organic-inorganic hybrid film has at least two peaks, the average circularity coefficient is preferably 0.80 or more, particularly preferably 0.90 or more, for particles with a particularly large mass, and typically the average circularity coefficient is 1.0 or less.
[0102] [Surface modifiers] The inorganic filler used in the present invention may be surface-modified. Here, the surface modification means that a compound capable of reacting with OH groups on the inorganic filler surface (hereinafter, sometimes referred to as a surface modifier) is reacted with the inorganic filler surface to bond the surface modifier to the inorganic filler surface.
[0103] The surface modifier used here is not particularly limited as long as it is a commonly used one, but from the viewpoint of reactivity with OH groups, silazanes, siloxanes, alkoxysilanes, chlorosilanes, titanate coupling agents, silicate oligomers, and the like can be preferably used.
[0104] Examples of the silazanes include hexamethyldisilazane and hexaethyldisilazane.
[0105] Examples of siloxanes include hexamethyldisiloxane, hexaethoxydisiloxane, 1,3-butyltetramethyldisiloxane, 1,3-diphenyltetramethyldisiloxane, 1,3-divinyltetramethyldisiloxane, hexaethyldisiloxane, 3-glycidoxypropylpentamethyldisiloxane, methylhydrogenpolysiloxane, and 1,3-dichloro-1,1,3,3-tetra-i-propyldisiloxane.
[0106] Examples of alkoxysilanes include vinyltrimethoxysilane, vinyltriethoxysilane, propenyltrimethoxysilane, propenyltriethoxysilane, butenyltrimethoxysilane, butenyltriethoxysilane, pentenyltrimethoxysilane, pentenyltriethoxysilane, hexenyltrimethoxysilane, hexenyltriethoxysilane, heptenyltrimethoxysilane, heptenyltriethoxysilane, octenyltrimethoxysilane, octenyltriethoxysilane, nonenyltrimethoxysilane, nonenyltriethoxysilane, dekenyltrimethoxysilane, dekenyltriethoxysilane, undekenyltrimethoxysilane, undekenyltriethoxysilane, dodekenyltrimethoxysilane, and dodekenyltriethoxysilane, as well as β-(3,4-Epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-acryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimeth Xysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-ureidopropyltriethoxysilane, tetraethoxysilane, tetramethoxysilane, tetrapropoxysilane, tetrabutoxysilane, methyltriethoxysilane, trimethylmethoxysilane, trimethylethoxysilane Silane, trimethylpropoxysilane, phenyldimethylmethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, dimethyldiethoxysilane, propyltriethoxysilane, n-butyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-octylmethyldiethoxysilane, n-decyltrimethoxysilane, n-octadecyltrimethoxysilane, phenyltrimethoxysilane, phenylmethyldimethoxysilane, phenethyltrimethoxysilane, dodecyltrimethoxysilane Silane, n-octadecyltriethoxysilane, diphenyldimethoxysilane, vinyltris(β-methoxyethoxy)silane, 3-isocyanatopropyltriethoxysilane, trifluoropropyltrimethoxysilane, heptadecatrifluoropropyltrimethoxysilane, n-decyltrimethoxysilane, dimethoxydiethoxysilane, bis(triethoxysilyl)ethane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxymethylsilane, 3-aminopropyldimethylethoxysilane, etc.,
[0107] Among the alkoxysilanes, those having an alkenyl group are preferred, and those having a vinyl group are particularly preferred. In the alkoxysilanes having a vinyl group, the number of carbon atoms in the chain having the vinyl group is usually 2 or more, preferably 5 or more, more preferably 7 or more, and usually 20 or less, preferably 15 or less, more preferably 12 or less. When the number of carbon atoms is within this range, the chain having the vinyl group has good affinity with the matrix resin and / or the precursor of the matrix resin, and the inhibition of the penetration and adsorption of gas into the inorganic filler by the chain having the vinyl group is reduced, so that the inorganic filler can be well dispersed in any one or more of the matrix resin precursor, the matrix resin intermediate, and the matrix resin while maintaining the performance of the inorganic filler. The alkoxysilanes may be commercially available, for example, KBM-1083 or X-12-1290 (both manufactured by Shin-Etsu Chemical Co., Ltd.).
[0108] Examples of chlorosilanes include vinyltrichlorosilane, trimethylsilyl chloride, triethylsilyl chloride, t-butyldimethylsilyl chloride, tri-i-propylsilyl chloride, and 3-isocyanopropyldimethylchlorosilane.
[0109] Examples of the silicate oligomer include methyl silicate oligomers such as MS51, MS56, MS57, and MS56S manufactured by Mitsubishi Chemical Corporation.
[0110] Among these surface modifiers, those whose terminals react with the matrix resin precursor and / or the matrix resin intermediate are particularly preferably used. That is, when the matrix resin precursor and / or the matrix resin intermediate is an addition reaction type silicone resin, a surface modifier having a vinyl terminal is preferably used. Among the surface modifiers having a vinyl terminal, vinyl-terminated alkoxysilanes are preferred, and vinyl-terminated trimethoxysilanes are preferred, from the viewpoints of reactivity and ease of handling.
[0111] Among these surface modifiers, a surface modifier having a good affinity between the group that does not react with the inorganic filler and the resin can more effectively disperse the inorganic filler in the matrix resin. On the other hand, it is preferable that the surface modifier is less likely to inhibit the gas adsorption and gas permeability of the inorganic filler such as zeolite, which exerts a molecular sieve effect due to the pores. In this respect, the carbon number of the group that does not react with the inorganic filler is usually 2 or more, preferably 5 or more, more preferably 7 or more, and usually 20 or less, preferably 15 or less, more preferably 12 or less.
[0112] By modifying the surface with these surface modifiers, the affinity between the inorganic filler and the organic solvent used in film formation is increased, and the dispersibility of the inorganic filler is increased in a mixture of one or more of the matrix resin, matrix precursor, and matrix resin intermediate, inorganic filler, and solvent used in film formation, making it easier to obtain an organic-inorganic hybrid film with a high inorganic filler filling rate.
[0113] In addition, by modifying the surface of the inorganic filler with these surface modifiers, the affinity between the inorganic filler and the matrix resin is improved and voids are less likely to occur at the interface between the inorganic filler and the matrix resin, making it easier to obtain an organic-inorganic hybrid membrane composite equipped with an organic-inorganic hybrid membrane that has high separation and permeation performance and fully utilizes the performance of the inorganic filler.
[0114] On the other hand, since the pores of inorganic fillers such as zeolites, which have a molecular sieve effect due to their pores, can be blocked by surface modifiers, it is desirable to keep the modification of inorganic fillers with surface modifiers to a minimum.
[0115] Methods for modifying the surface with these surface modifiers include: a method in which the inorganic filler and the surface modifier are placed in an appropriate solvent and reacted while being heated and stirred as necessary; a method in which the surface modifier is supplied to the inorganic filler by steam and reacted; and a method in which the inorganic filler and the surface modifier are kneaded together to react. When reacting, it is desirable to thoroughly dry the inorganic filler to remove moisture from within the pores and modify only the surface, but from the viewpoint of promoting the reaction, it is also possible to react after allowing the inorganic filler to absorb moisture at an appropriate vapor pressure.
[0116] The surface modifier can be added when mixing any one or more of the matrix resin, the matrix precursor, and the matrix resin intermediate with the inorganic filler and, if necessary, with a solvent, so that a part of the surface modifier can be used as a surface modifier for the inorganic filler and a part of the surface modifier can be used as a dispersant, and as a material for improving leveling and handling properties. The surface modifier has a functional group that can react with the inorganic filler, and therefore is easily adsorbed or reacted with the inorganic filler. Therefore, by mixing the surface modifier as described above, the surface modifier is easily present on the inorganic filler surface, and the structural viscosity caused by the inorganic filler can be destroyed. In the surface modifier as described above, the organic group portion may come into contact with the polar portion of the inorganic filler, thereby functioning as a surfactant that eliminates the phase separation structure in the resin composition, and the dispersibility of the inorganic filler is improved, thereby improving the filling rate of the inorganic filler in the organic-inorganic hybrid film. That is, the surface modifier as described above may function as a dispersant when mixing the inorganic filler with any one or more of the matrix resin, the matrix precursor, and the matrix resin intermediate, and may also have the effect of improving the handling and leveling properties.
[0117] The proportion of the surface modifier when mixed is usually 1% or more, preferably 3% or more, more preferably 5% or more, and usually 50% or less, preferably 30% or less, more preferably 10% or less, based on the mass of the organic-inorganic hybrid film. When the proportion of the surface modifier is within the above range, the viscosity of the organic-inorganic hybrid film during film formation can be reduced. In addition, the dispersibility of the inorganic filler can be improved, and the long-term stability of the organic-inorganic hybrid film can be ensured. When the proportion of the surface modifier is below the upper limit, the proportion of the matrix resin increases, and the obtained organic-inorganic hybrid film becomes stronger and tends to be less prone to defects.
[0118] The zeolite used in the present invention may be ion-exchanged as necessary. In the case of a zeolite synthesized using a template, the ion-exchange is usually carried out after removing the template. Ions to be exchanged include protons and Na + , K + , Cs + , Li + Alkali metal ions such as Ca 2+ , Mg 2+ , Sr 2+ , B.A. 2+ Examples of suitable ions include ions of group 2 elements such as Ca, Fe, Cu, Zn, and Ag, and ions of transition metal elements such as Fe, Cu, Zn, and Ag. The pore size of zeolite and its affinity with gas molecules can be changed by ion exchange, so the preferred ions vary depending on the type of gas to be separated, but permeation performance can be improved by using ions with high affinity for the gas to be permeated. In the case of organic-inorganic hybrid membranes for CO2 separation, Ca is the most suitable from the viewpoint of affinity with CO2. 2+ , K + , Ag + The use of these ions tends to improve the CO2 permeability and the separation factor.
[0119] Ion exchange of zeolite can be carried out by the usual method, but in order to avoid blocking of zeolite pores, it is necessary to calcinate it after ion exchange and to remove NO3 - It is desirable to remove the counter anions such as these by thermal decomposition.
[0120] [Porous support layer] The organic-inorganic hybrid membrane of the present invention is formed on a porous support layer. Forming the membrane on a porous support layer is preferable because, compared with a case where the organic-inorganic hybrid membrane is a free-standing membrane alone, the durability of the entire organic-inorganic hybrid membrane composite and its resistance to external forces are increased, and the thickness of the organic-inorganic hybrid membrane can be made thinner.
[0121] The shape of the porous support layer is not particularly limited, but examples include a porous planar membrane, a porous hollow fiber membrane, and a nonwoven fabric, with a porous hollow fiber membrane being preferred since it allows a large membrane area per unit volume.
[0122] The pore size of the porous support layer is usually 10 μm or less, preferably 5 μm or less, more preferably 1 μm or less, further preferably 0.5 μm or less, particularly preferably 0.1 μm or less, and is usually 0.01 μm or more, preferably 0.02 μm or more.
[0123] When the pore size of the porous support layer is within the above range, the support layer does not impede gas permeation and can impart the necessary strength to the organic-inorganic hybrid membrane composite.
[0124] The porous support layer may have a symmetric structure or an asymmetric structure having a rough support layer below a dense surface layer. The asymmetric structure is preferred because it reduces the resistance caused by the porous support layer during gas permeation.
[0125] The thickness of the porous support layer is usually 10 μm or more, preferably 30 μm or more, more preferably 50 μm or more, even more preferably 70 μm or more, and particularly preferably 100 μm or more, and is usually 2 mm or less, preferably 1 mm or less, more preferably 500 μm or less, and particularly preferably 200 μm or less. When the thickness of the porous support layer is in this range, sufficient strength can be imparted to the organic-inorganic hybrid membrane composite.
[0126] [Measurement of the thickness of the porous support layer] The thickness of the porous support layer of the organic-inorganic hybrid membrane composite is calculated from the scanning electron microscope electron image of the cross section of the organic-inorganic hybrid membrane composite obtained by freeze fracture. When selecting the field of view of the scanning electron microscope electron image, the field of view in which the porous support layer has an average thickness is selected. It is important that the observation magnification of the scanning electron microscope can fully observe the thickness of the porous support layer over as wide an area as possible, and it is desirable to select the minimum magnification that allows the thickness of the porous support layer to be fully observed. That is, it is usually 100 times. For the scanning electron microscope electron image measured by the above method, at the interface between the separation-related layer and the support layer, both ends of the image are connected with a straight line, and at three points that divide the line into four equal parts, a line perpendicular to the line is drawn, and the length of the perpendicular line crossing the porous support layer is calculated, and the value calculated by arithmetically averaging the lengths at these three points is the thickness of the porous support layer.
[0127] The material of the porous support layer is not particularly limited, but is usually a polymer, preferably polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethersulfone (PES), polysulfone (PSU), cellulose acetate (CA), polyethylene (PE), polypropylene (PP), polycarbonate (PC), polyimide (PI), polyamide, more preferably polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethersulfone (PES), cellulose acetate (CA), particularly preferably polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). When the material of the porous support layer is one of these preferred polymers, the porous support layer has sufficient flexibility and strength, and does not impose any restrictions on the membrane production method of the organic-inorganic hybrid membrane, so that the organic-inorganic hybrid membrane composite can be given sufficient strength and excellent processability.
[0128] In the organic-inorganic hybrid membrane composite of the present invention, the organic-inorganic hybrid membrane may be formed directly on the porous support layer, i.e., the porous support layer and the organic-inorganic hybrid membrane may be in contact with each other, or the organic-inorganic hybrid membrane may be formed indirectly on the porous support layer, i.e., another layer such as a base layer may be interposed between the porous support layer and the organic-inorganic hybrid membrane.
[0129] [Permeation of resins constituting the separation-related layer into the porous support layer and its measurement] The porous support layer may be permeated with a portion of the matrix resin constituting the separation-related layer or the resin constituting the underlayer, that is, the resin constituting the separation-related layer.
[0130] The degree of penetration can be expressed, for example, by the occupancy ratio of the resin that has penetrated into the porous support layer in a region of 20 μm thickness from the interface between the separation-related layer and the porous support layer toward the porous support layer in the cross section of the organic-inorganic hybrid membrane composite. The occupancy ratio is usually 60% or less, preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, even more preferably 25% or less, and particularly preferably 20% or less, and is usually 3.0% or more, preferably 5.0% or more. By having the occupancy ratio within this range, a higher permeance can be realized, and the adhesion between the porous support layer and the separation-related layer is good, resulting in a membrane with excellent durability. In addition, when the thickness of the porous support layer is less than 20 μm, the region from the interface between the separation-related layer and the porous support layer to the lower end of the porous support layer is used to calculate the occupancy ratio. For example, when the thickness of the porous support layer is 15 μm, the occupancy ratio of the resin that has penetrated is calculated in the region of the porous support layer with a thickness of 15 μm in the cross section of the organic-inorganic hybrid membrane composite.
[0131] The occupancy ratio can be calculated by taking an image, such as element mapping, of a cross section obtained by cutting the organic-inorganic hybrid membrane composite along the lamination direction of the separation-related layer and the porous support layer, and analyzing the image. The element mapping can be mapping of elements contained in the resin constituting the separation-related layer and not contained in the porous support layer, for example, Si mapping. The specific calculation method is in accordance with the method described in the Examples.
[0132] [Base layer] The organic-inorganic hybrid membrane of the present invention may be formed on a porous support layer, but when forming a membrane on a porous support layer, it may be formed on a base layer (=gutter layer) formed on the porous support layer. By further providing a base layer between the organic-inorganic hybrid membrane and the porous support layer, the organic-inorganic hybrid membrane composite can avoid or reduce the occurrence of defects in the organic-inorganic hybrid membrane caused by excessive penetration of one or more of the matrix resin, matrix precursor, and matrix resin intermediate and the solvent used in the membrane formation into the porous support layer during the formation of the organic-inorganic hybrid membrane, and also, since the matrix resin, matrix precursor, and matrix resin intermediate and the solvent used in the membrane formation do not excessively penetrate into the porous support membrane, it is possible to form a thin and dense organic-inorganic hybrid membrane.
[0133] The material for forming the underlayer is not particularly limited, but typically silicone resin, polytrimethylsilylpropyne (PTMSP), polyethersulfone (PES), polysulfone (PSU), or polyethylene oxide (PEO) is used, preferably silicone resin, polytrimethylsilylpropyne (PTMSP), or polyethylene oxide (PEO), and particularly preferably silicone resin, because they have high solvent resistance, and therefore there are fewer restrictions on the film-forming method when forming a film on the underlayer, making them easy to handle.
[0134] The thickness of the underlayer is preferably as thin as possible in order to reduce the permeation resistance of layers not related to separation, but is usually 1 nm or more, preferably 10 nm or more, and usually 3 μm or less, preferably 1.5 μm or less, more preferably 500 nm or less. In addition, the underlayer may be at least partially integrated with the organic-inorganic hybrid membrane in the obtained organic-inorganic hybrid membrane composite by being solubilized in a solvent used for forming the organic-inorganic hybrid membrane.
[0135] [Protective layer] In the present invention, an organic-inorganic hybrid membrane composite having a protective layer formed on the opposite side of the porous support layer across the organic-inorganic hybrid membrane serving as the separation layer can also be used for gas separation.
[0136] The material for forming the protective layer is not particularly limited, but typically silicone resin, polytrimethylsilylpropyne (PTMSP), polyethersulfone (PES), polysulfone (PSU), or polyethylene oxide (PEO) is used, preferably silicone resin, polytrimethylsilylpropyne (PTMSP), or polyethylene oxide (PEO), and particularly preferably silicone resin, which are preferably used because they have high gas permeability and little effect on the performance of the organic-inorganic hybrid membrane that is the separation layer.
[0137] It is preferable that the protective layer is absent in order not to prevent the permeation of the separation layer, but when the protective layer is necessary for protecting the separation layer, it is desirable to make the protective layer have a minimum thickness that sufficiently protects the separation layer in order not to prevent the permeation of the separation layer. The thickness of the protective layer is usually 1 nm or more, preferably 10 nm or more, more preferably 100 nm or more, and usually 100 μm or less, preferably 10 μm or less, more preferably 1 μm or less.
[0138] The performance of an organic-inorganic hybrid membrane composite is expressed by the permeability and separation performance of the composite.
[0139] The permeability of an organic-inorganic hybrid membrane composite is represented by the gas permeability coefficient (hereinafter sometimes referred to as the permeability coefficient), i.e., Permeability, or gas permeability (hereinafter sometimes referred to as the permeability), i.e., Permeance, of the organic-inorganic hybrid membrane composite.
[0140] [Transmission coefficient] Gas permeability coefficient P of gas A A [Barrer]=P A ×10 -10 [cm 3 cm / (cm 2 The permeation rate (m / s·cmHg) of gas A permeates the organic-inorganic hybrid membrane composite, divided by the difference between the supply pressure and the permeation pressure, multiplied by the membrane thickness of the organic-inorganic hybrid membrane composite excluding the porous support layer (hereinafter, the portion of the organic-inorganic hybrid membrane composite excluding the porous support layer may be referred to as the separation-related layer), and is expressed by the following formula (1). P A ×10 -10 =N A l / (p2-p1) (1) In formula (1), N A : Permeation flux (permeation amount per unit time divided by membrane area of the composite) [cm ] at steady state when gas A permeates the composite 3 (STP) / (cm 2 s)] l: Thickness of the separation-related layer, i.e., the part of the organic-inorganic hybrid membrane composite excluding the porous support layer [cm] p1: Partial pressure of gas A on the permeation side [cmHg] p2: Partial pressure of gas A on the supply side [cmHg] means...
[0141] The preferred range of the CO2 permeability coefficient of the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is usually 9000 Barrer or more, preferably 9500 Barrer or more, more preferably 10000 Barrer or more, particularly preferably 12000 Barrer or more, and most preferably 15000 Barrer or more, and the upper limit is not particularly limited, but is usually 100,000,000 Barrer or less. When the gas permeability coefficient is within this range, the gas processing amount of the organic-inorganic hybrid membrane composite is sufficient, and the composite can be used in an actual process.
[0142] [Permeance] Gas permeability R of gas A A [mol / (m 2 ·s·Pa)] is the permeation amount per unit area when gas A permeates the organic-inorganic hybrid membrane composite divided by the difference between the supply pressure and the permeation pressure, and is expressed by the following formula (2). R A =n A / (p2'-p1')···(2) In formula (2), n A : The steady-state permeation flux (permeation amount per unit time divided by the membrane area of the composite) [mol / (m 2 s)] p1': partial pressure of gas A on the permeation side [Pa] p2': Partial pressure of gas A on the supply side [Pa] means...
[0143] Permeance can also be expressed in units of [GPU], and in this specification, 1 GPU = 3.35 × 10 -10 mol / (m 2 s Pa).
[0144] The preferred range of CO2 permeability of the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is usually 500 GPU or more, preferably 600 GPU or more, more preferably 1000 GPU or more, even more preferably 1200 GPU or more, and particularly preferably 1500 GPU or more, and the upper limit is not particularly limited, but is usually 100000 GPU or less, preferably 50000 GPU or less, more preferably 10000 GPU or less, and even more preferably 6000 GPU or less. When the CO2 permeability is within this range, the gas processing amount of the organic-inorganic hybrid membrane composite is sufficient, and the composite can be used in an actual process.
[0145] [Separation factor] Separation factor α of gas A against gas B AB is the permeability coefficient P of gas A A and the permeability coefficient P of gas B B , or the permeability R of gas A A and the permeability R of gas B B Using this, it is expressed by the following formula (3). α AB =P A / P B =R A / R B (3)
[0146] A preferred range of the separation factor exhibited by the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is, for example, in the case of the CO2 / CH4 separation factor, usually 5 or more, preferably 7 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 17 or more, and the upper limit is not particularly limited, but is usually not more than 1000. When the separation factor is within this range, in gas separation using the organic-inorganic hybrid membrane composite, the amount of gas that is mixed into the permeation side and cannot be separated is reduced, enabling efficient separation.
[0147] A preferred range of the separation factor exhibited by the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is, for example, in the case of a CO2 / N2 separation factor, usually 11 or more, preferably 13 or more, more preferably 15 or more, even more preferably 20 or more, particularly preferably 25 or more, and most preferably 30 or more, and the upper limit is not particularly limited, but is usually 300 or less, preferably 100 or less, more preferably 70 or less. When the separation factor is within this range, in gas separation using the organic-inorganic hybrid membrane composite, the amount of gas that is mixed into the permeation side and cannot be separated is reduced, enabling efficient separation.
[0148] In addition, the gas permeability coefficient, gas permeability, and separation factor are calculated by measuring the steady-state gas permeation flux of the composite by the constant volume / valuable pressure method (Journal of Polymer Science: Part B: Polymer Physics, Vol. 38, 2051-2062 (2000)) using a single component gas or a mixed gas.
[0149] [Air permeability] The air permeability of the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is 10,000 L / (m 2 When the air permeability is in this range, the organic-inorganic hybrid membrane composite has no or reduced defects, and can therefore be suitably used as a separation membrane. From the same viewpoint, the air permeability of the organic-inorganic hybrid membrane composite is preferably 5000 L / (m 2 ·h), and more preferably 2000 L / (m 2 ·h), and more preferably 1000 L / (m 2 ·h), and particularly preferably 800 L / (m 2 ·h), and more preferably 650 L / (m 2 ·h) or less, most preferably 350 L / (m 2 The permeation rate is preferably 0.0 L / (m 2 ·h) or more, for example, 20L / (m 2 h) or more, for example 50L / (m 2When the air permeability is in this range, there are no defects or through holes or the effects of these are sufficiently small, so that high separation performance can be exhibited.
[0150] Here, the air permeability is the amount of air permeated [unit: L / (m2)] when the organic-inorganic hybrid membrane composite set in the module is placed under atmospheric pressure and one side of the organic-inorganic hybrid membrane composite is connected to a vacuum line of 5 kPa, as described in detail in the Examples section. 2 ·h)] (0°C, 1 atm equivalent).
[0151] The air permeability can be adjusted by, for example, adjusting the type of matrix resin, the thickness of the organic-inorganic hybrid film, and the content of inorganic filler in the organic-inorganic hybrid film.
[0152] [Film thickness] In the organic-inorganic hybrid membrane composite according to one embodiment of the present invention, the thickness of the organic-inorganic hybrid membrane is usually 0.05 μm or more, preferably 0.1 μm or more, more preferably 1 μm or more, and more preferably 2 μm or more, and usually 15 μm or less, preferably 13 μm or less, more preferably 11 μm or less, and more preferably 10 μm or less. In the organic-inorganic hybrid membrane composite, when there is an underlayer and / or a protective layer, the organic-inorganic hybrid membrane is integrated with the underlayer and the protective layer, so that it may be difficult to determine the thickness of each layer. In addition, when the organic-inorganic hybrid membrane is integrated with the underlayer and / or the protective layer, the underlayer and the protective layer also contribute to the gas permeability and separation property, so that the thickness of the part excluding the porous support layer (hereinafter, this part may be referred to as the separation-related layer) may be important in the organic-inorganic hybrid membrane composite. In the organic-inorganic hybrid membrane composite, the thickness of the separation-related layer is usually 0.05 μm or more, preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more, and may be usually 15 μm or less, preferably 13 μm or less, more preferably 11 μm or less, and even more preferably 10 μm or less. When the thickness of the separation-related layer is in this range, a dense membrane without defects or through holes is easily formed, and it is possible to achieve both high separation performance and high permeance. In addition, the organic-inorganic hybrid membrane composite comprising the organic-inorganic hybrid membrane and the porous support layer has high permeability and is durable. In addition, the composite has sufficient flexibility with excellent processability and resistance to bending, and can be modularized without cracks or pinholes occurring in the organic-inorganic hybrid membrane.
[0153] [Film thickness measurement] For free-standing organic-inorganic hybrid films, the thickness is measured using a Digimatic standard outside micrometer (Mitutoyo Corporation, MDC-25M) or a high-precision digital length measuring machine (Mitutoyo Corporation, Litematic VL-50S-B) to calculate the arithmetic mean of four locations: the center of the film to be measured and three locations slightly inward from the edge of the film, selected so as to be evenly spaced around the circumference.
[0154] In the case of an organic-inorganic hybrid membrane composite, the thickness is calculated from a scanning electron microscope electron image of the cross section of the organic-inorganic hybrid membrane composite obtained by freeze fracture. When selecting the field of view of the scanning electron microscope electron image, a field of view in which the thickness of the separation-related layer, which is the part other than the porous support layer, is average should be selected. It is important that the observation magnification of the scanning electron microscope can observe the thickness sufficiently over as wide an area as possible, and it is desirable to select the minimum magnification that allows sufficient observation of the thickness. That is, when the thickness of the separation-related layer is greater than 20 μm, it should be measured at 500 times, when it is 5 μm or more and 20 μm or less, it should be 2000 times, and when it is less than 5 μm, it should be measured at 500 times or more. For the scanning electron microscope electron image measured by the above method, at the interface between the separation-related layer and the support layer, both ends of the image are connected with a straight line, and at each of the three points that divide the line into four equal parts, a line perpendicular to the line is drawn, and the length of the perpendicular line crossing the separation-related layer is calculated, and the value calculated by arithmetically averaging the lengths at these three points is the thickness of the separation-related layer. The thickness of the organic-inorganic hybrid membrane is measured in the same manner.
[0155] [Ratio of the arithmetic mean roughness of the organic-inorganic hybrid membrane surface to the thickness of the separation-related layer] The arithmetic mean surface roughness of the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is the arithmetic mean surface roughness of the surface of the organic-inorganic hybrid membrane opposite to the support layer side.
[0156] In general, it is believed that when gas molecules pass through an organic-inorganic hybrid membrane composite, the gas molecules are adsorbed to the surface of the organic-inorganic hybrid membrane composite and diffuse into the interior of the organic-inorganic hybrid membrane composite. The greater the surface roughness of the organic-inorganic hybrid membrane, the greater the surface area of the organic-inorganic hybrid membrane, which is advantageous for the adsorption of gas molecules, and is therefore believed to contribute to improving the permeability of the gas molecules. In addition, the surface roughness of the organic-inorganic hybrid membrane composite is believed to be mainly due to the formation of convex portions caused by the inorganic filler protruding from the matrix resin surface. The greater the surface roughness, the more the inorganic filler with high gas selectivity protrudes from the surface of the matrix resin, which also contributes to improving gas selectivity when gas molecules are adsorbed on the surface.
[0157] The gas permeability and separation performance of an organic-inorganic hybrid membrane composite are influenced not only by the gas adsorption and selectivity of the surface, but also by the gas diffusion and selectivity in the separation-related layer, and the larger the thickness of the separation-related layer, the greater the effect on the gas diffusion and selectivity in the separation-related layer. In other words, when the surface roughness of an inorganic hybrid membrane composite is the same, the smaller the thickness of the separation-related layer, the greater the effect of the surface roughness on the gas permeability and separation performance, and the larger the thickness of the separation-related layer, the smaller the effect of the surface roughness on the permeability and separation performance. Therefore, when considering the contribution of the surface roughness of an organic-inorganic hybrid membrane composite to the gas permeability and separation performance, it is necessary to consider the surface roughness relative to the thickness of the separation-related layer.
[0158] The ratio of the arithmetic mean surface roughness (Ra) of the organic-inorganic hybrid membrane composite surface to the thickness of the separation-related layer (Ra (nm) / thickness of separation-related layer (nm)) is usually 0.050 or more, preferably 0.070 or more, more preferably 0.10 or more, and usually 2 or less, preferably 1 or less. When the value of Ra (nm) / thickness of separation-related layer (nm) is within this range, the gas permeability is improved due to the effect of the surface unevenness, and the gas separation performance is improved due to the inorganic filler with high gas selectivity near the surface.
[0159] The arithmetic mean surface roughness Ra of the surface of the organic-inorganic hybrid film composite may reflect the unevenness caused by protrusions of the inorganic filler, or may be due to the unevenness of the support layer or underlayer.
[0160] [Method of measuring arithmetic mean surface roughness] The arithmetic mean surface roughness Ra of the organic-inorganic hybrid film composite surface was measured by observing the surface of the organic-inorganic hybrid film composite with a 50x objective lens using a laser microscope, selecting five fields of view with average surface conditions, and measuring the arithmetic mean surface roughness Ra of four randomly selected points within a 50μm square range in each field of view. The arithmetic mean surface roughness Ra of the organic-inorganic hybrid film composite surface was calculated by taking the arithmetic mean of the arithmetic mean surface roughness Ra of the 20 points (5 fields of view x 4 ranges) in total. The calculation of Ra in each field of view was performed based on JIS B0601:2001 (ISO 4287:1997).
[0161] [Maximum ratio of maximum length of continuous inorganic filler in organic-inorganic hybrid film] In an organic-inorganic hybrid membrane composite, the higher the proportion of inorganic filler with gas selectivity in the gas flow path of the separation-related layer, the higher the gas permeability and separation ability. In addition, since the interface between the inorganic filler and the matrix resin, where gas permeability changes, hinders gas permeation, the smaller the interface, even with the same filler proportion, the higher the gas permeability and separation ability.
[0162] That is, in the organic-inorganic hybrid membrane composite, the cross section of the organic-inorganic hybrid membrane composite created by BIB processing (broad ion beam processing, argon atmosphere) under cooling conditions was magnified 1000 times in a backscattered electron image of a scanning electron microscope, and the continuous maximum length of the inorganic filler having gas selectivity, which is crossed by a line extending perpendicularly from a straight line connecting the interface points of the porous support layer and the separation-related layer at both ends of the image, was divided by the length of the separation-related layer crossed by the line extending perpendicularly, which is the film thickness of the separation-related layer, and the maximum value of the ratio of the maximum length of the continuous inorganic filler (hereinafter referred to as the maximum continuous maximum ratio of the inorganic filler) was obtained. The larger the maximum value of the continuous maximum ratio of the inorganic filler, the higher the gas permeability and separation ability. In addition, when the inorganic fillers are in contact with each other, the continuous maximum length is calculated for the multiple inorganic fillers that are in contact with each other. The maximum value of the ratio of the maximum continuous length of the inorganic filler to the film thickness of the separation-related layer is usually 20% or more, preferably 30% or more, more preferably 50% or more, even more preferably 60% or more, particularly preferably 70% or more, and most preferably 80% or more, and may usually be 100% or less, preferably 95% or less.
[0163] [Ratio of average maximum length of continuous inorganic fillers in organic-inorganic hybrid films] In an organic-inorganic hybrid membrane composite, the higher the proportion of inorganic filler with gas selectivity in the gas flow path of the separation-related layer, the higher the gas permeability and separation ability. In addition, since the interface between the inorganic filler and the matrix resin, where gas permeability changes, hinders gas permeation, the smaller the interface, even with the same filler proportion, the higher the gas permeability and separation ability.
[0164] That is, in the case of an organic-inorganic hybrid membrane composite, in a backscattered electron image of a scanning electron microscope obtained at a magnification of 1000 times of a cross section of an organic-inorganic hybrid membrane composite prepared by BIB processing (argon atmosphere) under cooling conditions, a straight line is drawn connecting the interface points between the porous support layer and the separation-related layer at both ends of the image for three average fields of view, and a line perpendicular to the line is drawn at each of the three points that divide the line into four equal parts, and the ratio of the maximum length of the part where the inorganic filler having selectivity for the gas that the perpendicular line crosses is continuous to the length of the separation-related layer that the perpendicular line crosses, which is the film thickness of the separation-related layer, is determined, and the arithmetic mean of the values for a total of nine points is calculated to be the average maximum continuous length ratio of the inorganic filler.
[0165] The larger the average continuous maximum length ratio of the inorganic filler, the higher the gas permeability and separation property. The average continuous maximum length ratio of the inorganic filler is usually 20% or more, preferably 30% or more, more preferably 40% or more, more preferably 50% or more, even more preferably 60% or more, particularly preferably 70% or more, most preferably 80% or more, and may be usually 100% or less, preferably 95% or less.
[0166] [Bending test] In an organic-inorganic hybrid membrane composite according to one embodiment of the present invention, the gas permeability coefficient and the gas permeability after a bending test in which the composite is bent once by 180° along a curved surface with a bending radius (curvature radius) of 3 mm, then stretched and returned to approximately the original shape are compared with the values before bending, and the absolute value of the change rate ((value before bending - value after bending test) / value before bending) is preferably 30% or less, more preferably 25% or less, more preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, particularly preferably 3% or less, and most preferably 2% or less. In addition, the separation factor value after the bending test is compared with the value before bending, and the change rate ((value before bending - value after bending test) / value before bending) is preferably 20% or less, more preferably 10% or less, particularly preferably 5% or less, and most preferably 3% or less. In the bending back test, the temperature is room temperature (15° C. or higher and 35° C. or lower). The organic-inorganic hybrid membrane may be held in a 180° bent state (a state in which the two regions of the organic-inorganic hybrid membrane composite divided by bending are parallel to each other) for 5 seconds or more and 10 seconds or less. In the bending back test, the time required from the start of bending to bending 180° is within 10 seconds, and the time required for stretching and returning to approximately the original shape is within 10 seconds. In the bending back test, the 180° bending along the curved surface with a bending radius of 3 mm may be achieved, for example, by wrapping the organic-inorganic hybrid membrane composite around a cylindrical tube with a diameter of 6 mm at 180°. In the bending back test, the part through which gas permeates in the permeation test of the organic-inorganic hybrid membrane composite is bent along the curved surface. The approximately original shape refers to a state in which the original shape is visually returned to. When the organic-inorganic hybrid membrane composite of the present invention satisfies the above-mentioned performance, the organic-inorganic hybrid membrane composite can be bent as necessary for use, and therefore has excellent processability, and can be processed into a spiral-type module or a pleated-type module without the occurrence of cracks or pinholes in the membrane.Furthermore, when the above performance is satisfied, it means that no cracks or pinholes will occur in the membrane even when the organic-inorganic hybrid membrane composite is bent at a high curvature, and therefore the composite can be formed into a hollow fiber membrane without generating cracks or pinholes.
[0167] <Gas separation membrane module> When the organic-inorganic hybrid membrane composite according to one embodiment of the present invention is used for industrial gas separation, it is desirable to modularize it. A gas separation membrane module equipped with the organic-inorganic hybrid membrane composite is also included in one embodiment of the present invention. Examples of modules include a spiral type, a hollow fiber type, a pleated type, a tubular type, and a plate and frame type, and the spiral type (spiral wound type or SW type) or the hollow fiber type is preferred.
[0168] <Method of manufacturing organic-inorganic hybrid membrane composite> A method for producing an organic-inorganic hybrid membrane according to one embodiment of the present invention includes a dispersion step in which an inorganic filler having gas selectivity is dispersed in at least one of a precursor and an intermediate of a matrix resin and, if necessary, in a solvent; a casting step in which a dispersion liquid in which an inorganic filler is dispersed in at least one of a precursor and an intermediate of a matrix resin and, if necessary, in a solvent is supported or applied on a flat or curved surface of a porous support layer; and a curing step in which the solvent of the cast dispersion liquid is removed, at least one of the precursor and the intermediate of the matrix resin is cured, and an organic-inorganic hybrid membrane is formed on the porous support layer. As a pre-step of the dispersion step, a kneading step in which a precursor of a polymer compound constituting the matrix resin and an inorganic filler having gas selectivity are kneaded together, or a dilution step in which the mixture obtained by the kneading step is diluted with a solvent may be further included. In the curing step in which the resin is cured, a step of curing the precursor of the matrix resin while applying pressure may further be included. In the step of curing the precursor of the matrix resin while applying pressure, it is preferable to heat the resin in order to promote curing.
[0169] When the polymer compound is thermoplastic, the polymer compound may be dissolved in a solvent, mixed with an inorganic filler, and cast to form a film.
[0170] In the method for producing an organic-inorganic hybrid film of the present invention, the casting step involves casting by applying or supporting on a porous support layer (an underlayer may be formed on the porous support layer) using a die coater, a blade or bar coater, a spin coater, immersion, immersion and suction, etc. Furthermore, the method for producing an organic-inorganic hybrid film of the present invention may further include an underlayer formation step of forming an underlayer on the porous support layer prior to the casting step.
[0171] [Mixing process] The method for producing an organic-inorganic hybrid film according to one embodiment of the present invention may include a kneading step. The kneading step is a step of kneading a precursor of a polymer compound contained in a matrix resin with an inorganic filler having gas selectivity. In the kneading step, in order to improve dispersibility, leveling property, and handling property, any one or more of a surface modifier and a dispersant may be added and kneaded with the precursor of the polymer compound contained in the matrix resin and the inorganic filler. In this specification, kneading has a meaning generally understood by those skilled in the art, and for example, means an operation of kneading a precursor of a matrix resin with an inorganic filler under conditions in which at least a part of the precursor of the polymer compound contained in the matrix resin is not dissolved in a solvent, but is not limited thereto.
[0172] In the kneading process, a high shear force is applied to the inorganic filler by kneading the mixture, and the aggregated secondary particles are dispersed as primary particles, thereby improving the dispersibility of the inorganic filler. Conventionally, when a composition containing a resin and particles is produced by kneading the mixture, a large amount of resin is adsorbed on the particle surface, and the particles are coated, so that the properties derived from the particles, such as electrical conductivity and thermal conductivity, may not be exhibited in the composition. However, in the present invention, since the matrix resin has a certain degree of gas permeability, the gas permeability and separation performance derived from the inorganic filler are fully exhibited even when the inorganic filler particles are coated in the organic-inorganic hybrid membrane.
[0173] In the kneading step, the mixing ratio of the matrix resin and the inorganic filler can be appropriately adjusted, and is preferably adjusted so as to obtain the above-mentioned preferred content of the inorganic filler.
[0174] In addition, the mixing ratio of the matrix resin and the inorganic filler may be adjusted so that the viscosity of the mixture obtained by the kneading process is in a desired numerical range. By adjusting the viscosity of the mixture obtained, the shear force applied to the inorganic filler in the kneading process can be adjusted, and the dispersibility of the inorganic filler can be further improved. For example, the kneading process may obtain a mixture having a viscosity of preferably 30 Pa·s or more, more preferably 40 Pa·s or more, and even more preferably 50 Pa·s or more. In addition, the upper limit of the viscosity of the mixture obtained is not particularly limited from the viewpoint of applying a high shear force to the inorganic filler. For example, the kneading process may obtain a mixture having a viscosity of preferably 500 Pa·s or less, more preferably 300 Pa·s or less, from the viewpoint of reducing the load applied to the device used in the kneading process. In this specification, the viscosity refers to the viscosity measured at 25°C using a cone-plate type viscometer.
[0175] Examples of the method for kneading in the kneading step include a method using a mixer, a bead mill, a ball mill, a twin-screw kneader, a three-roll mill, a planetary centrifugal mixer, etc. In addition, in the kneading step, additives such as a curing agent may be added within a range in which the shear force applied to the inorganic filler is not too low.
[0176] The inorganic filler before being kneaded is preferably sufficiently dried. The temperature at which the inorganic filler is dried before being kneaded with any one or more of the matrix resin precursor, intermediate, and matrix resin is usually 100°C or higher, preferably 120°C or higher, more preferably 150°C or higher, even more preferably 200°C or higher, and usually 300°C or lower, and the drying time is usually 3 hours or higher, preferably 5 hours or higher, more preferably 8 hours or higher, even more preferably 12 hours or higher, and usually 48 hours or lower, preferably 30 hours or lower, and more preferably 20 hours or lower. When the drying temperature and time are within this range, the moisture in the zeolite can be sufficiently removed within an economical time.
[0177] [Dilution process] The dilution step in the present invention is a step of mixing a solvent with a mixture of at least one of a matrix resin precursor, a matrix resin intermediate, and a matrix resin, and an inorganic filler having gas selectivity. In the dilution step, at least one of a surface modifier and a dispersant may be added and diluted with a solvent in the presence of these for the purpose of improving dispersibility, leveling property, and handling property. The mixture may have a high viscosity and may be difficult to form into a film. However, by carrying out the dilution step, the viscosity of the mixture in which the primary particles of the inorganic filler are dispersed can be adjusted, making it easier to form a film. In the dilution step when the kneading step is carried out, the mixture obtained by the kneading step is diluted by mixing it with a solvent.
[0178] The solvent is not particularly limited as long as it dissolves the matrix resin, the matrix precursor, or the matrix resin intermediate, and toluene, hexane, ethyl acetate, methyl ethyl ketone, N-methylpyrrolidone, etc. can be used, but a solvent that has good dispersibility of the inorganic filler is preferred. While most of the matrix resins or the polymer compound precursors or intermediates contained in the matrix resins are hydrophobic, the surface of inorganic fillers such as zeolite is hydrophilic, so a solvent with moderate polarity such as ethyl acetate or methyl ethyl ketone is preferred.
[0179] The ratio of the solvent to the inorganic filler varies depending on the amount of the inorganic filler and the type of resin, but it is preferable to adjust the amount of the solvent so as to obtain a viscosity that facilitates film formation according to the film formation method.
[0180] The method of mixing the mixture with the solvent may include, in addition to normal stirring and kneading, ultrasonic disintegration, dispersion, a planetary centrifugal mixer, etc. In addition, in the dilution step, an additive such as a curing agent may be added to the mixture.
[0181] [Dispersion process] The dispersion step in the present invention refers to a step of dispersing an inorganic filler in one or more of a precursor, intermediate, and matrix resin of a matrix resin and, if necessary, a solvent. Specifically, after thoroughly drying the inorganic filler, one or more of a precursor, intermediate, and matrix resin of a matrix resin dissolved in a solvent, or a solvent-free precursor and / or a matrix resin intermediate, and an inorganic filler are thoroughly mixed to thoroughly disperse the inorganic filler, and then, when a resin requiring a curing agent is used, a curing agent is further added and thoroughly mixed to disperse the inorganic filler. At this time, after dispersing the inorganic filler in a solvent, one or more of a precursor, intermediate, and matrix resin of a matrix resin can be added and thoroughly mixed to disperse the inorganic filler. Methods for dispersing an inorganic filler include stirring with a normal mixer, a bead mill, a ball mill, etc., kneading with a twin-shaft kneader or a three-roll mill, as well as ultrasonic disintegration, dispersion, and the use of a rotation / revolution mixer. In the dispersion step, one or more of a surface modifier and a dispersant may be added for the purpose of improving dispersibility, leveling property, and handling property. The dispersion step includes the kneading step and the dilution step.
[0182] The solvent is not particularly limited as long as it is a solvent in which the matrix resin or any one or more of the matrix resin precursor, intermediate, and matrix resin can be dissolved, and toluene, hexane, ethyl acetate, methyl ethyl ketone, N-methylpyrrolidone, etc. can be used, but a solvent with good dispersibility of the inorganic filler is preferable. While many of the matrix resin or any one or more of the matrix resin precursor, intermediate, and matrix resin are hydrophobic, the surface of inorganic fillers such as zeolite is hydrophilic, so a solvent with moderate polarity such as ethyl acetate or methyl ethyl ketone is preferable.
[0183] [Casting process] The casting process is a process of supporting or applying the dispersion of the inorganic filler, the precursor of the matrix resin, the intermediate, the matrix resin, and the solvent obtained in the dispersing process onto a flat or curved surface. Examples of the flat or curved surface on which the dispersion is supported include the inner or outer surface of a hollow fiber-shaped porous support layer, the upper surface of a flat membrane-shaped porous support layer, and the upper surface of a base layer formed on a porous support layer.
[0184] As for the method of application or support, when a flat porous support layer is used, application with a die coater, blade, bar coater or spin coater is preferred, a die coater, blade or bar coater is more preferred, and a die coater or blade is particularly preferred.
[0185] When a hollow fiber-shaped porous support layer is used, the dispersion may be supported on the support layer by a method such as impregnation, suction, or pressure to form a membrane.
[0186] If necessary, a base layer may be formed on the porous support layer in advance, and then a film may be formed on the base layer. The base layer may be formed by any method known to those skilled in the art, and may be formed, for example, by applying any of the substances described above as the substance for forming the base layer onto the porous support layer and heating the substance to harden it.
[0187] [Curing process] In the present invention, after the casting step, the solvent is removed, and then a curing step is carried out to crosslink and / or cure the precursor or intermediate of the matrix resin. In the curing step, a pressure curing step is preferably carried out in which the resin is cured while applying pressure to the organic-inorganic hybrid film. By curing the precursor and / or intermediate of the matrix resin while applying pressure, an organic-inorganic hybrid film without or with reduced voids can be produced even if the inorganic filler is filled in a large amount.
[0188] The curing step is a step of removing the solvent from the dispersion liquid that has been applied, supported, and cast in the casting step, and then curing the resin under a predetermined curing condition. After the casting step, the solvent is removed using a vacuum dryer, and the resin is cured at a predetermined curing temperature for a predetermined curing time, or the resin is cured while volatilizing the solvent under a nitrogen stream using an inert oven, thereby obtaining an organic-inorganic hybrid film.
[0189] The temperature conditions of the vacuum dryer are changed appropriately depending on the solvent used. The curing temperature and curing time are also set to conditions suitable for the resin used.
[0190] In the curing step, it is more preferable to cure the precursor and / or intermediate of the matrix resin while applying pressure. By curing the precursor and / or intermediate of the matrix resin while applying pressure, an organic-inorganic hybrid film without or with reduced voids can be produced even if the inorganic filler is highly filled.
[0191] When silicone rubber obtained by curing polyorganosiloxane is used as the matrix resin, it is usually preferable to mix the inorganic filler with the polyorganosiloxane before curing, but this is not limiting.
[0192] The means for curing the curable polyorganosiloxane is not particularly limited, and a conventionally known method can be adopted, but from the viewpoint of productivity, it is preferable to use a method that easily proceeds with the reaction. In this respect, it is preferable to use a type that is cured by addition reaction, condensation reaction, ultraviolet light, radiation, or electron beam irradiation, and it is particularly preferable to use addition reaction or condensation reaction.
[0193] In the film formation, the polymer compound contained in the matrix resin is preferably cured or softened and then solidified while applying pressure to the organic-inorganic hybrid film. By curing the resin while applying pressure, a film without or with reduced voids can be produced even if the inorganic filler is filled in a large amount.
[0194] There are various methods for applying pressure in the curing step, but it is preferable to apply pressure while heating. As a method for applying pressure while heating, for example, a method of applying pressure to the film by heating and curing using a heat press, a vacuum heat press, a vacuum laminating device, a double belt press, or the like is preferable.
[0195] The pressure in the curing step is usually 1 MPa or more, preferably 2 MPa or more, more preferably 3 MPa or more, even more preferably 4 MPa or more, and particularly preferably 5 MPa or more, and is usually 30 MPa or less, preferably 20 MPa or less, more preferably 10 MPa or less, and even more preferably 8 MPa or less. When the pressure is within the above range, it is possible to obtain a film with a high inorganic filler loading amount without destroying the pores of the inorganic filler in the organic-inorganic hybrid film and without any voids between the inorganic filler and the matrix resin.
[0196] The heating temperature and heating time may be appropriately determined depending on the hardening or softening / solidification conditions of the polymer compound contained in the matrix resin used, but the heating time under pressure is usually 1 minute or more, preferably 5 minutes or more, more preferably 10 minutes or more, and usually 2 hours or less, preferably 1 hour or less. When it is within this range, a film without or with reduced voids can be efficiently produced.
[0197] [Underlying layer formation process] The underlayer forming step in the present invention is a step of forming an underlayer on the porous support layer before the casting step. The underlayer can be formed by any method known to those skilled in the art, and may be, for example, a method of applying any of the substances described above as the substance for forming the underlayer onto the porous support layer, and then heating the substance to harden it.
[0198] [Modification of manufacturing method] In the present invention, the method for producing the organic-inorganic hybrid film and the organic-inorganic hybrid film composite is not limited to the above-mentioned embodiment. For example, in the present invention, the casting step may be performed by forming a sacrificial film on a flat or curved surface and supporting the dispersion obtained in the dispersion step on the sacrificial film. The sacrificial film is a film that is soluble in a solvent that does not dissolve the substrate that functions as a flat or curved surface and the organic-inorganic hybrid film. After performing such a casting step and the subsequent curing step, the obtained structure in which the substrate, the sacrificial film, and the organic-inorganic hybrid film are laminated in this order is immersed in a solvent that does not dissolve the substrate and the organic-inorganic hybrid film but dissolves the sacrificial film, so that the organic-inorganic hybrid film can be peeled off from the substrate without damaging it. As the sacrificial film and the solvent that dissolves the sacrificial film, those known in the art can be used.
[0199] Alternatively, the sacrificial film may be dissolved to peel the organic-inorganic hybrid film from the substrate, and the resulting film may be scooped up onto a porous support film and then dried to produce an organic-inorganic hybrid film composite.
[0200] <Gas separation and / or gas concentration method> The organic-inorganic hybrid membrane composite according to one embodiment of the present invention can separate and / or concentrate a gas mixture. A method for performing at least one of gas separation and gas concentration using the organic-inorganic hybrid membrane composite is also included in one embodiment of the present invention. The gas mixture used in the gas separation and / or gas concentration method according to one embodiment of the present invention includes at least one component selected from carbon dioxide, hydrogen, oxygen, nitrogen, methane, ethane, ethylene, propane, propylene, normal butane, isobutane, 1-butene, 2-butene, isobutene, sulfur hexafluoride, helium, carbon monoxide, nitric oxide, and water. Among the components of the gas mixture containing the gas, gas components with high permeance (hereinafter sometimes referred to as gas permeability) permeate the organic-inorganic hybrid membrane and are separated and / or concentrated, and gas components with low gas permeability are concentrated on the supply gas side.
[0201] Further, the gas mixture is more preferably one containing at least two of the above-mentioned components. In this case, the two components are preferably a combination of a component with high gas permeability and a component with low gas permeability.
[0202] The gas separation of the present invention is preferably used for the separation and concentration of CO2, H2, oxygen, or nitrogen, and is particularly preferably used for the separation and concentration of CO2.
[0203] Methods for separating and concentrating CO2 include removing carbon dioxide from natural gas (CO2, CH4 mixture), capturing CO2 from landfill gas (CO2, CH4 mixture), capturing CO2 from artificial fermentation gas (CO2, CH4 mixture), and capturing CO2 from combustion exhaust gas (CO2, N2 mixture) from thermal power plants, etc.
[0204] Examples of hydrogen separation and concentration include hydrogen recovery in the oil refining industry, hydrogen recovery and purification in various reaction processes in the chemical industry (H2, CO, CO2, hydrocarbon mixtures), and the production of high-purity hydrogen for fuel cells. Hydrogen for fuel cells is produced by the steam reforming reaction of methane, and it is necessary to separate hydrogen from a mixed gas of hydrogen, carbon monoxide, methane, and water.
[0205] Other applications include the production of oxygen-enriched gas from air (for medical use, oxygen-enriched air for combustion, etc.) as a means of oxygen separation and concentration, and the production of nitrogen-enriched gas from air by nitrogen separation and concentration (for explosion prevention, oxidation prevention, etc.).
[0206] A known method can be used for gas separation. A pressure difference is created between the gas supply side and the gas permeation side of the membrane, and gas that is easily permeable from the mixed gas on the supply side is allowed to permeate to the permeation side. At this time, the mixed gas on the gas supply side may be pressurized, or the permeation side may be depressurized using a vacuum pump or the like, or both may be used.
[0207] The pressure difference between the gas supply side and the permeation side is desirably set to an optimum pressure for the process to be applied, and is usually 0.01 MPa or more, preferably 0.05 MPa or more, more preferably 0.08 MPa or more, and even more preferably 0.1 MPa or more, and is usually 20 MPa or less, preferably 10 MPa or less, more preferably 5 MPa or less, even more preferably 1 MPa or less, even more preferably 0.5 MPa or less, and particularly preferably 0.2 MPa or less.
[0208] In the gas separation and / or concentration method according to one embodiment of the present invention, a sweep gas may be used. A method using a sweep gas is a method in which any gas is caused to flow on the permeation side and the gas that has permeated the membrane is collected.
[0209] The pressure of the sweep gas is usually atmospheric pressure, but is not particularly limited, and is usually 10 MPa or less, preferably 5 MPa or less, more preferably 1 MPa or less, even more preferably 0.5 MPa or less, particularly preferably 0.1 MPa or less, and most preferably 0.05 MPa or less, and the lower limit is usually 0.0 MPa or more.
[0210] In a gas separation and / or concentration method according to one embodiment of the present invention, the temperature of the supply gas and the membrane may be the optimum temperature for each process, but is usually 100°C or less, preferably 80°C or less, more preferably 50°C or less, and even more preferably 40°C or less, and is usually -30°C or more, preferably -15°C or more, more preferably 0°C or more, even more preferably 5°C or more, particularly preferably 10°C or more, and most preferably 20°C or more. EXAMPLES
[0211] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the present invention. In the following description, it is easy for a person skilled in the art to understand whether the sample referred to is a composite having a porous support layer and an organic-inorganic hybrid membrane, or a free-standing membrane having an organic-inorganic hybrid membrane without a porous support layer. Therefore, in the following description, the organic-inorganic hybrid membrane composite (sometimes abbreviated as composite) and the organic-inorganic hybrid membrane (sometimes abbreviated as membrane) may be understood as interchangeable depending on the context.
[0212] The methods for producing, measuring and evaluating samples in the present invention are as follows.
[0213] [Powder X-ray diffraction (XRD) measurement method] The XRD measurements were carried out under the following conditions. Equipment: BRUKER D2 PHASER X-ray source: Cu-Kα ray Output setting: 30kV 10mA Divergence slit: 0.3° Soller slit on entrance side: 2.5° Solar slit on light receiving side: 2.5° Detection unit opening angle: 5.69° Ni filter: 2.5% Diffraction peak position: 2θ (diffraction angle) Measurement range: 2θ=5~50° Scan speed: 0.05°(2θ / sec)
[0214] [Method of measuring SiO2 / Al2O3 molar ratio (SAR)] The SiO2 / Al2O3 molar ratio was determined by XRF after preparing a calibration curve in advance by ICP analysis and XRF.
[0215] The zeolite sample was dissolved by heating in an aqueous hydrochloric acid solution, and the silicon atom and aluminum atom contents (mass%) were determined by ICP analysis. A calibration curve was then created between the fluorescent X-ray intensity of the analyzed element in the standard sample and the atomic concentration of the analyzed element. Using this calibration curve, the silicon atom and aluminum atom contents (mass%) in the zeolite sample were determined by XRF. The ICP analysis was performed using an ULTIMA 2C manufactured by Horiba Ltd. The XRF measurements were performed using an EDX-700 manufactured by Shimadzu Corporation or a fluorescent X-ray analyzer Supermini200 manufactured by Rigaku Corporation.
[0216] [Method of measuring average particle size] The particle size of the inorganic filler used in the organic-inorganic hybrid film was measured by dispersing the synthesized powder well to prepare a sample, taking pictures with a JEOL JSM-6010LV scanning electron microscope at an accelerating voltage of 10 kV, and analyzing the images of 30 randomly selected particles with Mac-View, an image analysis type particle size distribution measurement software made by Mountec Co., Ltd., to determine the particle size, and the arithmetic mean of the particle sizes was used as the average particle size. For secondary particles formed by agglomeration of small crystal particles, this refers to the secondary particle size.
[0217] The particle diameter of the inorganic filler in the obtained organic-inorganic hybrid film was measured by photographing the cross section of the organic-inorganic hybrid film obtained by freeze-fracturing using a FE-SEM (Hitachi: S-4500 or JEOL Ltd.: JSM-6701F) at an accelerating voltage of 10 kV, and 30 particles of the inorganic filler randomly selected from the cross section were subjected to image analysis using Mac-View, an image analysis type particle size distribution measurement software manufactured by Mountech Co., Ltd., to determine the particle diameter. The arithmetic mean of the particle diameters was used as the average particle diameter.
[0218] In either method, the particle size is defined as the diameter of a circle having an area equal to the projected area of the particle (equivalent circle diameter).
[0219] [Method of measuring average circularity coefficient] The particle size of the inorganic filler used in the organic-inorganic hybrid film was measured by dispersing the synthesized powder well to prepare a sample, taking pictures with a JEOL JSM-6010LV scanning electron microscope at an accelerating voltage of 10 kV, and analyzing the images of 30 randomly selected particles with Mac-View, an image analysis type particle size distribution measurement software manufactured by Mountec Co., Ltd., to determine the circularity coefficient, and the arithmetic mean of the circularity coefficients was used as the average circularity coefficient. For secondary particles formed by agglomeration of small crystal particles, the average of the circularity coefficients of the secondary particles was used as the average circularity coefficient.
[0220] The circularity coefficient here is 4πS / L, where S is the area of the two-dimensional projected image of the inorganic filler particle used, and L is the perimeter of the particle. 2 It is a value expressed as:
[0221] [Method of measuring particle size distribution] The particle size distribution of the inorganic filler used in the organic-inorganic hybrid film was measured under the following conditions. - Device name: Laser diffraction / scattering particle size distribution measuring device LA-950 (manufactured by Horiba, Ltd.) ·Measurement method: Mie scattering theory Measurement range: 0.01~3000μm Light source: Semiconductor laser (650nm) Detector: Ring-shaped silicon photodiode Dispersion solvent: Water
[0222] The inorganic filler was thoroughly dispersed in water using an ultrasonic cleaner, and the dispersion was dropped into a flow cell filled with water, and the particle size distribution was measured within a range of appropriate light intensity. The peak particle size was determined from the obtained volumetric particle size distribution.
[0223] [Single component gas permeation test] The single-component gas permeation test was carried out using the apparatus shown in FIG. 1, using the constant volume / valuable pressure method.
[0224] (Pretreatment of organic-inorganic hybrid membrane composite) As a pretreatment of the organic-inorganic hybrid membrane composite prior to the gas permeation test, the composite 1 set in the separation membrane module 2 was heated to 80°C or higher in a thermostatic chamber for two hours while reducing the pressure in both the supply line and the permeation line. After two hours, the temperature of the thermostatic chamber was lowered to 35°C and held for one hour to remove water and gas dissolved and adsorbed in the composite.
[0225] (Single component gas permeation and separation test) The permeation side of the composite (the lower side of the composite in Figure 1) was reduced in pressure to 13 Pa (absolute pressure) or less, and gas was supplied at a constant pressure of about 35 kPa (G), and the permeation coefficient was calculated from the rate of pressure increase on the permeation side when the pressure difference between the supply side and the permeation side of the composite was set to 0.1 MPa. The temperature of the thermostatic bath was set to 35°C, and the permeation coefficient of the composite at 35°C was calculated.
[0226] Gas was supplied from gas cylinder 18, and hand valve 17 and valve 13 on the secondary side of mass flow controller 5 were opened to supply gas through mass flow controller 5, and after storing the gas to be used in the permeation test at about 35 kPa (G) in gas supply reservoir 3, valve 12 was closed and valve 11 was opened at the same time to supply gas to the composite. At this time, valve 14 was open and valve 15 was closed. In order to keep the pressure of the supply gas constant, a constant amount of gas was supplied through mass flow controller 5 with valve 13 open, and the pressure was kept constant by exhaust pressure valve 6.
[0227] The permeability coefficient was calculated from the pressure increase rate after the pressure increase rate measured by the pressure gauge 7 became steady, the volume from the lower side of the composite to the valve 12, the membrane thickness, and the membrane area. The gas reservoir for the permeating gas was filled with water and the internal volume was measured from the amount of water, and the volume of the piping portion was calculated from the piping length and inner diameter, thereby calculating in advance the volume from the lower side of the composite to the valve 12. An absolute pressure transducer (MKS Baratron (registered trademark) for 0 to 10 Torr (626C11TBE)) was used as the pressure gauge.
[0228] The gases used were carbon dioxide (purity 99.9%, manufactured by Toho Oxygen Industries Co., Ltd.), methane (purity 99.999%, manufactured by Japan Fine Products), and hydrogen (purity 99.99%, manufactured by Showa Denko Gas Products Co., Ltd.).
[0229] [Mixed gas permeation and separation test] The mixed gas permeation and separation test was performed using the device shown in FIG.
[0230] (Pretreatment of organic-inorganic hybrid membrane composite) As a pretreatment of the organic-inorganic hybrid membrane composite prior to the gas permeation separation test, the organic-inorganic hybrid membrane composite 26 set in the separation membrane module 25 was heated to 35° C. in a thermostatic chamber 27 and held for 3 hours while supplying carbon dioxide (purity 99.9%, manufactured by Toho Oxygen Industry Co., Ltd.) to the separation membrane module 25. The pressure on the permeation side was atmospheric pressure.
[0231] (Mixed gas permeation and separation test) Following the pretreatment, after confirming that the flow rate on the permeation side of the mass flow meter 23 was stable, carbon dioxide (purity 99.9%, manufactured by Toho Oxygen Industries Co., Ltd.) was supplied to the organic-inorganic hybrid membrane using the mass flow controllers 31 and 32 so that the ratio of carbon dioxide (purity 99.9995% or more, manufactured by Japan Fine Products Co., Ltd.) and nitrogen (purity 99.999%, manufactured by Japan Fine Products Co., Ltd.) was approximately 1:1. At this time, the pressure on the supply side was adjusted to 0.3 MPaG by the exhaust pressure valve 22. The permeation side was set to atmospheric pressure. The permeation gas was introduced into the gas chromatograph 19 by the flow path selection valve 20. The composition of the permeation gas analyzed by the gas chromatograph 19 when the flow rate of the mass flow meter 23 and the area ratio of the two gases in the permeation gas obtained by analysis with the gas chromatograph 19 were stable was taken as the composition of the permeation gas. The composition of the permeable gas was calculated from the area ratio of CO2 and CH4 or CO2 and N2, and was taken as the arithmetic mean of three analytical values. The permeation flow rate of each gas was calculated from the value of the mass flow meter 23, the composition determined by the gas chromatograph 19, and the calibration curve of each gas of the mass flow meter 23 that had been prepared in advance, and the sum of these was taken as the total permeation flow rate. The permeance of each gas was calculated from the permeation flow rate of each gas, the permeable gas composition, and the composition of the supply gas, and the permeance ratio of CO2 and CH4 was taken as the separation factor α CO2 / CH4 The ratio of CO2 and N2 permeance is the separation factor α CO2 / N2 It was decided.
[0232] The flow path was switched by the flow path selection valve 20, and the gas that did not permeate was supplied to the separation membrane module 25 by the gas chromatograph 19. The gas that did not permeate, i.e., the gas on the retentate side (passing side) (hereinafter, sometimes referred to as the passing gas), was introduced and analyzed by gas chromatography in the same manner to obtain the composition of the passing gas. The composition of the passing gas was also determined as the arithmetic mean value of the values analyzed three times.
[0233] A GC3210 manufactured by GL Sciences Inc. was used as the gas chromatograph 19. The detector of the GC3210 was a TCD, and He was used as the carrier gas. The permeable gas or passing gas collected using a 0.5 ml sampling loop was introduced into the column online using the carrier gas. From the peak area ratio of CO2 and CH4 or CO2 and N2, the composition of each gas was calculated using a calibration curve created in advance using a mixed gas of known gas composition. The arithmetic mean of the values analyzed three times was taken as the composition of the permeable gas.
[0234] [Film thickness measurement] The film thickness was measured by a scanning electron microscope as shown below.
[0235] In the case of an organic-inorganic hybrid membrane composite, the cross section of the organic-inorganic hybrid membrane composite obtained by freeze-fracturing is calculated from an electron image of a scanning electron microscope. When selecting the field of view of the electron image of the scanning electron microscope, a field of view in which the membrane thickness of the separation-related layer, which is the part other than the porous support layer, is average is selected.
[0236] It is important that the magnification of the scanning electron microscope can observe the film thickness sufficiently over as wide an area as possible, and it is desirable to use the lowest magnification that allows sufficient observation of the film thickness. That is, when the film thickness of the separation-related layer is greater than 20 μm, it should be measured at 500 times, when it is 5 μm or more and 20 μm or less, it should be measured at 2000 times, and when it is less than 5 μm, it should be measured at 5000 times or more. For the electron image of the scanning electron microscope measured by the above method, at the interface between the separation-related layer and the support layer, both ends of the image are connected with a straight line, and at three points that divide the line into four equal parts, a line perpendicular to the line is drawn, and the length of the perpendicular line crossing the separation-related layer is calculated, and the value calculated by arithmetically averaging the lengths at these three points is regarded as the film thickness of the separation-related layer.
[0237] For free-standing organic-inorganic hybrid films, the film thickness is calculated from the arithmetic mean of four locations, including the center of the film and three locations slightly inward from the edge of the film, selected evenly around the circumference, using a Digimatic standard outside micrometer (MDC-25M, manufactured by Mitutoyo Corporation) or a high-precision digital length measuring machine (Litematic VL-50S-B, manufactured by Mitutoyo Corporation).
[0238] The conditions for acquiring the scanning electron microscope images are as follows. ·Equipment: FE-SEM Hitachi: S-4500 Or Scanning Electron Microscope JEOL Ltd.: JSM-6701F Acceleration voltage: 10kV ·Acquired image: secondary electron image
[0239] [Measurement of glass transition temperature] The glass transition temperature was measured using a differential scanning calorimeter (DSC) or a thermomechanical analyzer (TMA).
[0240] (Method 1 for measuring glass transition temperature using DSC) The glass transition temperature measurement method 1 by DSC was measured using a differential scanning calorimeter DSC6220 (Au sensor) manufactured by Hitachi High-Tech Science Corporation. Approximately 10 mg of the resin sample was placed in an aluminum sample container and sealed, and heated from room temperature to 150°C at a heating rate of 10°C / min under a nitrogen gas flow of 50 mL / min. After holding the temperature for 5 minutes, the sample was taken out of the furnace and quenched in liquid nitrogen, and then heated again from -150°C to 150°C at a rate of 10°C / min. The inflection point of the DSC data obtained in the second heating was taken as the glass transition temperature.
[0241] (Method 2 for measuring glass transition temperature using DSC) The measurement method 2 of the glass transition temperature by DSC was measured using a DSC600 manufactured by Hitachi High-Tech Science Corporation. Approximately 10 mg of a resin sample was placed in an aluminum sample container and crimped, and the temperature was raised from room temperature to 150°C at a heating rate of 10°C / min under a nitrogen gas flow of 30 mL / min. After holding the temperature for 1 minute, the sample was rapidly cooled to -150°C at a setting of 100°C / min, and the temperature was held for 35 minutes, after which the temperature was raised again from -150°C to 150°C at a rate of 10°C / min. The inflection point of the DSC data obtained in the second heating was taken as the glass transition temperature.
[0242] (Measurement of glass transition temperature by TMA) The glass transition temperature was measured by TMA using a thermomechanical analyzer TMA / SS6100 manufactured by SII NanoTechnology, Inc., and was determined from the mutation point of the thermal expansion coefficient. The sample had a width of 4 mm and a chuck distance of 20 mm, and was measured by applying a tensile load of 49 mN and raising the temperature from 30°C to 325°C at a heating rate of 10°C / min.
[0243] [Measurement of the weight average molecular weight of the main polyorganosiloxane before curing in terms of polystyrene by GPC] The polystyrene-equivalent weight average molecular weight of the main polyorganosiloxane before curing, which is the matrix resin precursor or the matrix resin intermediate, was measured by GPC using either of the following GPC measurement methods 1 or 2.
[0244] (GPC measurement method 1) The measurements were carried out using a Tosoh HLC-8420GPC. The sample was adjusted to about 0.25 w / w% using chloroform solvent, and then 10 μL was injected into a series-connected column of HK-404L (Shodex, 4.5×150 mm, 3.5 μm) and HK-401 (Shodex, 4.6×150 mm, 3 μm) held at 40° C., and chloroform supplied at a flow rate of 0.65 mL / min was used as the eluent.
[0245] The detector used was RI detection (polarity: -), and the arithmetic average of the weight-average molecular weight values measured twice was taken to obtain the polystyrene-equivalent weight-average molecular weight of the main polyorganosiloxane before curing. Note that monodisperse polystyrene was used as the calibration sample for the weight-average molecular weight, and the calibration method was polystyrene-equivalent using a third-order calibration curve approximation equation.
[0246] (GPC measurement method 2) Measurements were performed using an LC-30A (Nexera) manufactured by Shimadzu Corporation and a Corona UltraRS manufactured by Thermo Fisher Scientific. The sample was adjusted to approximately 0.1 w / w% using chloroform solvent, and 20 μL was injected into two PLgel Mixed-C (Agilent Technologies, 7.5 × 300 mm) columns connected in series and kept at 40°C. Chloroform was supplied at a flow rate of 1.0 mL / min as the eluent.
[0247] A CAD (Range: 500pA, Filter: 1, NEB: 35℃) was used as a detector, and the arithmetic mean of the weight average molecular weight measured twice was taken to obtain the polystyrene equivalent weight average molecular weight of the main polyorganosiloxane before curing. Note that monodisperse polystyrene was used as a calibration sample for the weight average molecular weight, and the calibration method was polystyrene equivalent using a third-order calibration curve approximation equation.
[0248] [Air permeability measurement] The porous support layer or the composite comprising the porous support layer and the organic-inorganic hybrid membrane was set in the module in a circular exposed state with a diameter of 1 cm, and one end of the module was connected to a 5 kPa vacuum line. The air flow rate was measured with a mass flow meter installed between the vacuum line and the module, and the air permeability [L / (m 2·h)] (0°C, 1 atm equivalent) was calculated. The mass flow meter used was Lintec's MM-2100M, for air gas, with a maximum flow rate of 20 mL / min (0°C, 1 atm equivalent). When the flow rate of the Lintec MM-2100M mass flow meter was greater than the maximum flow rate, KOFLOC's 8300, for N2 gas, with a maximum flow rate of 500 mL / min (20°C, 1 atm equivalent) was used. When the composite was set in the module, the side with the porous support layer was the reduced pressure side, i.e., the permeation side, and the side on which the organic-inorganic hybrid membrane was formed was the normal pressure side or pressurized side, i.e., the gas supply side.
[0249] [Measurement of the penetration of matrix resin into a porous support layer] The degree of infiltration of the matrix resin into the porous support layer of the organic-inorganic hybrid membrane composite was measured.
[0250] (Data acquisition method) Using an ArBlade5000 (Hitachi), BIB processing (using Ar gas) was performed under cooling conditions, followed by Pt coating (layer thickness 45 nm or less) to impart conductivity. The cross section of the resulting organic-inorganic hybrid film composite was photographed using a scanning electron microscope (SEM-EDS) while performing Si element mapping using EDS mapping measurement.
[0251] The measurement area was a region without obvious defects such as peeling of the film, where the organic-inorganic hybrid film was captured at the top of the image, the interface between the organic-inorganic hybrid film and the porous support layer was visually horizontal to the top of the measurement image, and the region included a range of about 5 μm from the interface toward the organic-inorganic hybrid film. A secondary electron image was obtained and Si element mapping (EDS mapping) was performed on this region.
[0252] (Secondary electron image measuring device) Equipment: SU5000 (HITACHI) Detector: High vacuum scintillator / photomultiplier secondary electron detector (Lower detector)
[0253] (Secondary electron image measurement conditions) Image resolution: 512 pixels x 384 pixels Acceleration voltage: 6kV ·WD(Working Distance):10±1mm Spot Intensity: 30 Measurement magnification: 3000x (observation field: 43μm×32μm)
[0254] (Backscattered electron image measuring device) Equipment: SU5000 (HITACHI) Detector: Retractable semiconductor backscattered electron detector (PD-BSD)
[0255] (Conditions for measuring backscattered electron images) Image resolution: 2560 pixels x 1920 pixels Acceleration voltage: 3kV WD (Working Distance): 7±2mm Spot Intensity: 30 Measurement magnification: 1000x (observation field: 127μm×95μm)
[0256] (EDS measurement equipment and software) Equipment: SU5000 (HITACHI) Detector: XFlash6 / 60 (Bruker) Measurement software: Esprit 2.3 (Bruker)
[0257] (EDS measurement conditions) Acceleration voltage: 6kV ·WD (Working Distance) 10±1mm Spot Intensity 30 Image resolution = 512 x 384 pixels -Duel time (capture time per pixel) = 16μs Pulse throughput = 60kcps Accumulation time = 600s EDS calibration: Calibrated to meet 10Kcps at an accelerating voltage of 15kV and Cu-Kα radiation using a copper standard.
[0258] (EDS analysis) Image processing software: Esprit 2.3 (Bruker) Method: Quantitative map analysis (tile size 2 x 2 pixels) Map display settings Image Filter = None Map Filter = None Result Format = Net Total Save format: A 512 pixel x 384 pixel image was expanded to 533 pixel x 400 pixel and saved in tif format.
[0259] (Data analysis method) The images obtained were analyzed and the degree of penetration was calculated. Image processing software: Esprit 2.3 (Bruker) Data processing methods: (1) Drawing of Si mapping image: The Si element (Kα line) detection intensity obtained under the condition of maximum depth of field is drawn so that it falls within the range of 0 to 150 in 8-bit grayscale value and the relationship between Si signal intensity and brightness is linear. This relationship between Si signal intensity and brightness was maintained by deconvolution processing and histogram flattening processing. (2) Occupancy ratio: A region of interest (ROI) is set for the Si mapping image thus obtained. Specifically, the region from the organic-inorganic hybrid film to the interface between the organic-inorganic hybrid film and the porous support layer is replaced with white (i.e., 255 in 8-bit grayscale). Next, the points where the brightness change is maximum are calculated in a 30-pixel-wide row on the left side of the measured image, and the point at the top of the image is set as the reference point for the ROI. The same process is performed for the 30-pixel-wide row on the right side of the measured image. The line segment connecting the determined right and left end reference points is translated by 20 μm in the direction from the interface toward the porous support layer, and the area further below the line segment is replaced with white (255 in 8-bit grayscale).
[0260] Next, the area that has not been replaced with white is set as the ROI. A histogram is drawn for the ROI with the Y axis representing the number of observed pixels and the X axis representing 8-bit grayscale values (0 to 254). The sum of the number of pixels with gradations of 20 to 254 divided by the sum of the number of pixels with gradations of 0 to 254 in the entire area is called the occupancy rate of the matrix resin in the ROI area, and is used as an index of the degree of penetration of the matrix resin into the porous support layer.
[0261] [Maximum ratio of maximum length of continuous inorganic filler in organic-inorganic hybrid film] Similar to the backscattered electron image measurement method in [Measurement of matrix resin penetration into porous support layer], for three average fields of view of 1000x backscattered electron images of the cross section obtained by BIB processing (using Ar gas) under cooled conditions, the maximum continuous length of particles intersected by a line extended perpendicularly from a straight line connecting the interface points between the porous support layer and the separation-related layer at both ends of the image was calculated, divided by the length of the separation-related layer intersected by the perpendicular line, and the maximum value of this was calculated to obtain the maximum ratio of the maximum continuous length of the inorganic filler (maximum ratio of maximum continuous length of inorganic filler).
[0262] [Ratio of average maximum length of continuous inorganic fillers in organic-inorganic hybrid films] Similar to the backscattered electron image measurement method in [Measurement of matrix resin penetration into porous support layer], for three average fields of view of 1000x backscattered electron images of the cross section obtained by BIB processing (using Ar gas) under cooling conditions, a straight line was drawn connecting the interface points between the porous support layer and the separation-related layer at both ends of the image, and perpendicular lines were drawn to each of the three points that divide the line into four equal parts. The ratio of the maximum length of the part where the inorganic filler having gas selectivity crossed by the perpendicular line was continuous to the length of the separation-related layer crossed by the perpendicular line, which is the film thickness of the separation-related layer, was determined, and the arithmetic mean of the values for a total of nine points was calculated to obtain the average maximum length ratio of continuous inorganic filler (average continuous maximum length ratio of inorganic filler).
[0263] [Arithmetic mean surface roughness] The arithmetic mean surface roughness Ra was measured for the organic-inorganic hybrid film composite. Using a laser microscope (VK-X200) manufactured by Keyence Corporation, five fields of view with average surface conditions were selected by observing with an objective lens of 50x magnification. Using an analysis application (VK-H1XA), the arithmetic mean surface roughness Ra was measured at four random points within a 50μm square range in each field of view, and the arithmetic mean surface roughness Ra was obtained for a total of 20 points (5 fields of view x 4 ranges). The arithmetic mean of the Ra for the total of 20 points was taken as the arithmetic mean surface roughness Ra of the organic-inorganic hybrid film composite. Ra was calculated based on JIS B0601:2001 (ISO 4287:1997).
[0264] [Synthesis of inorganic fillers with gas selectivity] Zeolite was synthesized as an inorganic filler with gas selectivity.
[0265] (Zeolite (Z-1)) 150g of 1mol / L-NaOH aqueous solution (Kishida Chemical Co., Ltd.) and 60g of 1mol / L-KOH aqueous solution (Kishida Chemical Co., Ltd.) were mixed, and 9.4g of aluminum hydroxide hydrate (Kyoward Co., Ltd.) was added and stirred to dissolve, and 128g of water was further added and stirred to obtain a transparent solution. 88.8g of N,N,N-trimethyl-1-adamanta ammonium hydroxide (TMADAOH) aqueous solution (containing 25% by mass of TMADAOH, Seichem Co., Ltd.) was added, and 225g of colloidal silica (Nissan Chemical Co., Ltd. Snowtech-40) was further added, and 1.8g of uncalcined CHA-type zeolite synthesized in the same manner as in JP-A-2016-104486 Production Example 9 was added as seed crystals, and the mixture was stirred for 2 hours to obtain a reaction mixture. TMADAOH was used as a structure-directing agent (SDA). The composition ratio of the obtained reaction mixture was 1.0SiO2 / 0.033Al2O3 / 0.1NaOH / 0.04KOH / 0.07TMADAOH / 20H2O, and the mass of the seed crystals was 2 mass% with respect to SiO2 in the reaction mixture.
[0266] The Teflon (registered trademark) inner cylinder (1 L) containing the reaction mixture was placed in a 1 L induction stirring autoclave and sealed, and the mixture was stirred at 100 rpm using an anchor impeller and heated at 160°C for 48 hours under autogenous pressure. After a predetermined time had passed, the mixture was allowed to cool, and the reaction mixture was removed, filtered, washed, and dried at 100°C for 5 hours or more to obtain as-made zeolite crystals. The as-made zeolite crystals were calcined at 550°C for 6 hours in an air atmosphere to pyrolyze the SDA, thereby obtaining zeolite (Z-1).
[0267] The obtained zeolite (Z-1) was subjected to powder X-ray diffraction analysis, and it was confirmed that the zeolite (Z-1) was a CHA-type zeolite. Since the zeolite (Z-1) is a CHA-type zeolite, it is an 8-membered oxygen ring zeolite, and the framework density (FD Si ) is 15.1. The average particle size of the obtained zeolite (Z-1) was 2 μm as a result of SEM observation, the shape was spherical, and the average circularity coefficient was 0.94. The SiO2 / Al2O3 ratio of the obtained zeolite (Z-1) was determined to be 26.
[0268] (Zeolite (Z-2)) Zeolite was synthesized in the same manner as Z-1, except that the composition ratio of the reaction mixture was 1.0SiO2 / 0.033Al2O3 / 0.1NaOH / 0.06KOH / 0.07TMADAOH / 20H2O, a pressure-resistant vessel with a capacity of 200 mL was used as the reaction vessel, and the vessel was rotated at 15 rpm in an oven at 160°C. Zeolite (Z-2) was obtained by synthesizing the zeolite and calcining it to remove SDA. Powder X-ray diffraction was measured for the obtained zeolite (Z-2), and it was confirmed that zeolite (Z-2) is a CHA-type zeolite. Since zeolite (Z-2) is a CHA-type zeolite, it is an oxygen 8-membered ring zeolite, and the framework density (FD Si ) is 15.1. The average particle size of the obtained zeolite (Z-2) was 1 μm as a result of SEM observation, and the SiO2 / Al2O3 ratio was found to be 26. The average circularity coefficient was 0.94.
[0269] (Zeolite (Z-3)) A zeolite was synthesized in the same manner as Z-2, except that Z-1 before calcination was used as the seed crystal, and Z-3 was obtained by calcining to remove SDA. The obtained zeolite (Z-3) was subjected to powder X-ray diffraction measurement, and it was confirmed that zeolite (Z-3) is a CHA-type zeolite. Since zeolite (Z-3) is a CHA-type zeolite, it is an oxygen 8-membered ring zeolite, and the framework density (FD Si ) is 15.1. The average particle size of the obtained zeolite (Z-3) was 0.8 μm as a result of SEM observation, and the SiO2 / Al2O3 ratio was 24. The average circularity coefficient was 0.92.
[0270] (Zeolite (Z-4)) Zeolite was synthesized in the same manner as Z-3, except that the composition ratio of the reaction mixture was 1.0SiO2 / 0.033Al2O3 / 0.1NaOH / 0.06KOH / 0.07TMADAOH / 100H2O, and zeolite (Z-4) was obtained by calcining and removing SDA. Powder X-ray diffraction was measured for the obtained zeolite (Z-4), and it was confirmed that zeolite (Z-4) is a CHA-type zeolite. Since zeolite (Z-4) is a CHA-type zeolite, it is an oxygen 8-membered ring zeolite, and the framework density (FD Si ) is 15.1. The average particle size of the obtained zeolite (Z-4) was 6 μm as a result of SEM observation, the shape was rugby ball-like, and the average circularity coefficient was 0.94. The SiO2 / Al2O3 ratio of the obtained zeolite (Z-4) was determined to be 25.
[0271] (Zeolite (Z-5)) 15 g of dried zeolite (Z-2) was added to 100 g of acetone measured in a round flask and 5 g of silane coupling agent (KBM-1083 Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated and refluxed at 55°C in an oil bath for 5 hours while stirring. After suction filtration, the mixture was thoroughly washed with acetone and dried to obtain zeolite (Z-5). The average particle size, SiO2 / Al2O3 ratio and average circularity coefficient of the obtained zeolite (Z-5) were the same as those of the raw material zeolite (Z-2).
[0272] (Zeolite (Z-6)) 15 g of dried zeolite (Z-3) was added to 100 g of acetone measured in a round-bottom flask and 5 g of silane coupling agent (KBM-1083 Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated and refluxed at 55°C in an oil bath for 5 hours while stirring. After suction filtration, the mixture was thoroughly washed with acetone and dried to obtain zeolite (Z-6). The average particle size, SiO2 / Al2O3 ratio and average circularity coefficient of the obtained zeolite (Z-6) were the same as those of the raw material zeolite (Z-3).
[0273] (Zeolite (Z-7)) 15 g of dried zeolite (Z-1) was added to 100 g of acetone measured in a round-bottom flask and 5 g of a silane coupling agent (KBM-1083, Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated and refluxed at 55°C in an oil bath for 5 hours while stirring. After suction filtration, the mixture was thoroughly washed with acetone and dried to obtain zeolite (Z-7). The average particle size, SiO2 / Al2O3 ratio, and average circularity coefficient of the obtained zeolite (Z-7) were the same as those of the raw material zeolite (Z-1).
[0274] (Zeolite (Z-8)) 15 g of dried zeolite (Z-4) was added to 100 g of acetone measured in a round-bottom flask and 5 g of silane coupling agent (KBM-1083 Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated and refluxed at 55°C in an oil bath for 5 hours while stirring. After suction filtration, the mixture was thoroughly washed with acetone and dried to obtain zeolite (Z-8). The average particle size, SiO2 / Al2O3 ratio and average circularity coefficient of the obtained zeolite (Z-8) were the same as those of the raw material zeolite (Z-4).
[0275] (Zeolite (Z-9)) 10 g of zeolite (Z-3) dried at 150°C for more than 12 hours was added to 100 g of hexamethyldisiloxane (HMDS) weighed into an eggplant flask, and the mixture was heated under reflux at 110°C for 5 hours in an oil bath while stirring. After suction filtration, the mixture was thoroughly washed with acetone and dried to obtain zeolite (Z-9). The average particle size, SiO2 / Al2O3 ratio and average circularity coefficient of the obtained zeolite (Z-9) were the same as those of the raw material zeolite (Z-3).
[0276] (Zeolite (Z-10)) Zeolite was synthesized in the same manner as Z-3, except that the composition ratio of the reaction mixture was 1.0SiO2 / 0.033Al2O3 / 0.1NaOH / 0.06KOH / 0.07TMADAOH / 60H2O, and zeolite (Z-10) was obtained by calcining and removing SDA. Powder X-ray diffraction was measured for the obtained zeolite (Z-10), and it was confirmed that zeolite (Z-10) is a CHA-type zeolite. Since zeolite (Z-10) is a CHA-type zeolite, it is an oxygen 8-membered ring zeolite, and the framework density (FD Si ) is 15.1. The average particle size of the obtained zeolite (Z-10) was 5 μm, the shape was rugby ball-like, and the average circularity coefficient was 0.94 as a result of SEM observation. The SiO2 / Al2O3 ratio of the obtained zeolite (Z-10) was found to be 24.
[0277] (Zeolite (Z-11)) 15 g of dried zeolite (Z-10) was added to a liquid of 100 g of acetone measured in a round flask and 5 g of a silane coupling agent (KBM-1083 Shin-Etsu Chemical Co., Ltd.), and the mixture was heated and refluxed in an oil bath at 55°C for 5 hours while stirring. After suction filtration, the mixture was thoroughly washed with acetone and dried to obtain zeolite (Z-11). The average particle size, SiO2 / Al2O3 ratio, and average circularity coefficient of the obtained zeolite (Z-11) were the same as those of the raw material zeolite (Z-10).
[0278] (Silicone resin / PVDF composite membrane (GL-1)) A porous PVDF membrane support layer with a pore size of 0.45 μm (Immobilon®-P membrane manufactured by Merck Millipore) was placed on a smooth plate, and silicone resin was applied using an applicator with a gap width of 1 mil. The resulting membrane was heated at 100° C. for 30 minutes to form a silicone resin underlayer. The composite membrane of the porous PVDF support layer and silicone resin is hereinafter referred to as silicone resin / PVDF composite membrane (GL-1). The thickness of the silicone resin layer in the silicone resin / PVDF composite membrane (GL-1) was 2 μm, as determined by observing the cross section obtained by freeze fracture with a scanning electron microscope.
[0279] (Silicone resin / PVDF composite membrane (GL-2)) A porous PVDF membrane support layer with a pore size of 0.45 μm (Immobilon®-P membrane manufactured by Merck Millipore) was placed on a smooth plate, and silicone resin was applied using an autocoater equipped with an applicator with a gap width of 0.5 mil. The resulting membrane was heated at 100° C. for 30 minutes to form a silicone resin underlayer. The composite membrane of the porous PVDF support layer and silicone resin is hereinafter referred to as silicone resin / PVDF composite membrane (GL-2). The thickness of the silicone resin layer in the silicone resin / PVDF composite membrane (GL-2) was 1 μm, as determined by observing the cross section obtained by freeze fracture with a scanning electron microscope.
[0280] (Organic-inorganic hybrid membrane complex (M-1)) 0.99 g of zeolite (Z-2) dried overnight at 150°C was weighed out, 0.602 g of silicone rubber precursor (SILPOT (registered trademark) 184 Silicone Elastomer Base (Dow Toray Industries, Inc.), hereinafter sometimes referred to as Silpot base agent) and 0.063 g of curing agent (SILPOT (registered trademark) 184 Silicone Elastomer Curing Agent (Dow Toray Industries, Inc.), hereinafter sometimes referred to as Silpot curing agent) were added, and the mixture was stirred for 14 minutes with a foaming mixer (Thinky Corporation), and then degassed for 1 minute. Furthermore, 1.348 g of hexane (Fujifilm Wako Pure Chemical Industries, Ltd.) was added and stirred with a stirrer to prepare a mixture to be used for film formation. A silicone resin / PVDF composite membrane (GL-1) was placed on a smooth plate, and the mixture was dropped on it and applied using an applicator with a gap width of 5 mil. After the solvent was removed using a vacuum dryer, the matrix resin was further cured by heating in a thermostatic chamber at 100°C for 30 minutes to obtain an organic-inorganic hybrid membrane composite (M-1). The matrix resin consisting of the cured product of the Silpot base agent and the Silpot hardener is hereinafter referred to as matrix resin (P-1). The solid content of the mixed solution used for membrane formation was 55% by mass, and the zeolite content in the organic-inorganic hybrid membrane was 59.8% by mass.
[0281] The cross section obtained by freeze-fracturing M-1 was observed with a scanning electron microscope, and the thickness of the organic-inorganic hybrid membrane and the underlayer combined, excluding the porous support layer from the organic-inorganic hybrid membrane composite (M-1), i.e., the separation-related layer, was measured. The thickness was 17 μm. The air permeability of the organic-inorganic hybrid membrane composite (M-1) was measured by the above-mentioned evaluation method, and was found to be 76 L / (m 2 ·h).
[0282] The CO2 permeability of the organic-inorganic hybrid membrane composite (M-1) at 35°C was 7400 Barrer, the CH4 permeability was 440 Barrer, and the CO2 permeability was 436 GPU at 35°C. The CO2 / CH4 ideal separation factor was 17.
[0283] The average value of the occupation ratio of three fields of view calculated from the sum of the Si areas with brightness of 20 to 254 / the sum of the Si areas with brightness of 0 to 254, which is an index showing the penetration of the silicone resin into the porous support layer, was 27%.
[0284] The arithmetic mean roughness Ra of the organic-inorganic hybrid membrane composite surface divided by the film thickness of the separation-related layer (Ra (nm) / film thickness of separation-related layer (nm)) was 0.043.
[0285] (Organic-inorganic hybrid membrane composite (M-2)) Zeolite (Z-7) 0.366g and Zeolite (Z-6) 0.079g were weighed out, which were dried overnight at 120℃, and Silpot base agent 0.174g and Silpot hardener 0.025g were added. The mixture was stirred with a foam remover mixer (Thinky Corporation) for 15 minutes, and then degassed for 1 minute. Furthermore, hexane (Fujifilm Wako Pure Chemical Industries, Ltd.) 0.445g was added and stirred with a stirrer to prepare a mixture for film formation. A silicone resin / PVDF composite film (GL-2) was placed on a smooth plate, and the mixture was dropped on it and applied using an applicator with a gap width of 5mil. After the solvent was removed with a vacuum dryer, a release film was placed on top and pressure was applied with a manual press (Imoto Manufacturing Co., Ltd. IMC-180C-C type) until the pressure gauge indicated 10MPa. The matrix resin was cured by heating to 100°C and holding for 5 minutes, and the release film was removed to obtain an organic-inorganic hybrid membrane composite (M-2). The solid content of the mixed solution used for membrane formation was 59 mass%, and the zeolite content in the organic-inorganic hybrid membrane was 69.1 mass%. Among the zeolites, the content of zeolite (Z-7) was 4.6 times that of zeolite (Z-6).
[0286] The cross section obtained by freeze-fracturing M-2 was observed under a scanning electron microscope, and the thickness of the organic-inorganic hybrid membrane and the underlayer combined, i.e., the separation-related layer, excluding the porous support layer from the organic-inorganic hybrid membrane composite (M-2) was measured, and found to be 28 μm. The air permeability of the organic-inorganic hybrid membrane composite (M-2) was measured by the above-mentioned evaluation method, and was found to be 0.0 L / (m2 ·h).
[0287] The average value of the occupation ratio of three fields of view calculated from the sum of the Si areas with brightness of 20 to 254 / the sum of the Si areas with brightness of 0 to 254, which is an index showing the penetration of the silicone resin into the porous support layer, was 40%.
[0288] The arithmetic mean roughness Ra of the organic-inorganic hybrid membrane composite surface divided by the film thickness of the separation-related layer (Ra (nm) / film thickness of separation-related layer (nm)) was 0.0076.
[0289] The maximum continuous maximum length ratio of the inorganic filler was 18%. The average continuous maximum length ratio of the inorganic filler was 7.6%.
[0290] The CO2 permeability of the organic-inorganic hybrid membrane composite (M-2) at 35°C was 8700 Barrer, the CH4 permeability was 450 Barrer, and the CO2 permeability was 312 GPU at 35°C. The CO2 / CH4 ideal separation factor was 20.
[0291] The permeation and separation performance of the organic-inorganic hybrid membrane composite (M-2) for the mixed gas of CO2 and CH4 was evaluated according to the method described above. In the pretreatment of the organic-inorganic hybrid membrane composite prior to the gas permeation and separation test, the flow rate of carbon dioxide supplied to the separation membrane module 25 was set to 37 sccm and the pressure was set to 0.2 MPaG.
[0292] The supply gas was a mixture of 74.7sccm CO2 and 78.5sccm CH4, supplied at 0.29MPaG. In other words, the CO2 concentration in the supply gas was 48.8%. The composition of the permeated gas was 91.7% CO2 and 8.3% CH4. The CO2 concentration in the passing gas was 48.5%, almost the same as the supply gas, and it was confirmed that the amount of supply gas was sufficient.
[0293] The permeance of CO2 in the CO2 / CH4 mixed gas permeation of M-2, calculated from the permeation amount of each permeation gas and the composition of the feed gas and permeation gas, is 8.7E-08mol / (m 2 ·s·Pa)(=260GPU) and the permeability coefficient was 7300 Barrer. The permeance of CH4 was 4.1E-09 mol / (m 2 The separation factor α calculated from the permeance ratio was CO2 / CH4 The separation factor was 21. By separating the mixed gas, the separation factor was slightly improved compared to the ideal separation factor calculated from the ratio of permeance measured with single gas. The permeance decreased slightly by using the mixed gas, but was roughly the same.
[0294] (Organic-inorganic hybrid membrane composite (M-3)) Zeolite (Z-4) 0.387g and zeolite (Z-5) 0.079g were weighed out after drying overnight at 120℃, and Silpot base agent 0.171g and Silpot hardener 0.015g were added. The mixture was stirred with a foaming mixer (Thinky Corporation) for 15 minutes and then degassed for 1 minute. Furthermore, hexane (Fujifilm Wako Pure Chemical Industries, Ltd.) 0.381g was added and stirred with a stirrer to prepare a mixture for film formation. A silicone resin / PVDF composite membrane (GL-2) was placed on a smooth plate, and the mixture was dropped onto it and applied using an applicator with a gap width of 2mil. After the solvent was removed with a vacuum dryer, the mixture was pressed in the same manner as the organic-inorganic hybrid membrane composite (M-2), except that the holding time at 100℃ was changed to 5 minutes, and the matrix resin was hardened to obtain an organic-inorganic hybrid membrane composite (M-3). The solid concentration of the mixed solution used for membrane formation was 63 mass%, and the zeolite content in the organic-inorganic hybrid membrane was 71.5 mass%. Among the zeolites, the content of zeolite (Z-4) was 4.9 times the content of zeolite (Z-5).
[0295] The cross section obtained by freeze-fracturing M-3 was observed with a scanning electron microscope, and the thickness of the organic-inorganic hybrid membrane and the underlayer combined, excluding the porous support layer from the organic-inorganic hybrid membrane composite (M-3), i.e., the separation-related layer, was measured. The thickness was 10 μm. The air permeability of the organic-inorganic hybrid membrane composite (M-3) was measured by the above-mentioned evaluation method, and was found to be 1.5 × 10 2 L / (m 2 ·h).
[0296] The CO2 permeability of the organic-inorganic hybrid membrane composite (M-3) at 35°C was 11,000 Barrer, the CH4 permeability was 680 Barrer, and the CO2 permeability was 1,100 GPU at 35°C. The CO2 / CH4 ideal separation factor was 16.
[0297] The average occupancy rate of three fields of view calculated as the sum of the Si areas with brightness of 20 to 254 / the sum of the Si areas with brightness of 0 to 254, which is an index showing the penetration of the silicone resin into the porous support layer, was 27%.
[0298] The arithmetic mean roughness Ra of the organic-inorganic hybrid membrane composite surface divided by the film thickness of the separation-related layer (Ra (nm) / film thickness of separation-related layer (nm)) was 0.079.
[0299] The maximum continuous maximum length ratio of the inorganic filler was 63%. The average continuous maximum length ratio of the inorganic filler was 34%.
[0300] (Organic-inorganic hybrid membrane composite (M-4)) The mixture was prepared in the same manner as M-1, except that the mixture was zeolite (Z-8 and Z-9) dried overnight at 120 °C, poly(dimethylsiloxane), hydroxyl-terminated (18,000-22,000 cSt, Sigma-Aldrich Japan), hexane (Fujifilm Wako Pure Chemical Industries, Ltd.), tetraethyl orthosilicate (Tokyo Chemical Industry Co., Ltd.), and dibutyltin dilaurate (Sigma-Aldrich Japan) in a weight ratio of 26:10:39:3:0.7, and then stirred at room temperature for 80 minutes. The mixture was used for membrane formation. A polyethersulfone membrane (hereinafter sometimes referred to as PES) immersed in desalted water (GVS Japan Co., Ltd.) was placed on a smooth plate, the water on the surface was removed, and the mixture was dropped onto the plate and applied using an applicator with a gap width of 2 mil. The solvent and water in the pores of the support layer were removed using a vacuum dryer to obtain an organic-inorganic hybrid membrane composite (M-4). The solid concentration of the mixed solution used for membrane formation was 48 mass%, and the zeolite content in the organic-inorganic hybrid membrane was 66.6 mass%. Among the zeolites, the content of zeolite (Z-8) was 3.5 times the content of zeolite (Z-9).
[0301] The cross section obtained by freeze-fracturing M-4 was observed with a scanning electron microscope, and the thickness of the organic-inorganic hybrid membrane, excluding the porous support layer from the organic-inorganic hybrid membrane composite (M-4), was measured. The thickness was 10 μm. The air permeability of the organic-inorganic hybrid membrane composite (M-4) was measured by the above-mentioned evaluation method, and was found to be 2.3 × 10 2 L / (m 2 ·h).
[0302] The CO2 permeability of the organic-inorganic hybrid membrane composite (M-4) at 35°C was 18,000 Barrer, the CH4 permeability was 960 Barrer, and the CO2 permeability was 1,750 GPU at 35°C. The CO2 / CH4 ideal separation factor was 18.
[0303] The average value of the occupation ratio of three fields of view calculated from the sum of the Si areas with brightness of 20 to 254 / the sum of the Si areas with brightness of 0 to 254, which is an index showing the penetration of the silicone resin into the porous support layer, was 18%.
[0304] The arithmetic mean roughness Ra of the organic-inorganic hybrid membrane composite surface divided by the film thickness of the separation-related layer (Ra (nm) / film thickness of separation-related layer (nm)) was 0.19.
[0305] The maximum continuous maximum length ratio of the inorganic filler was 92%. The average continuous maximum length ratio of the inorganic filler was 44%.
[0306] The permeation and separation performance of the organic-inorganic hybrid membrane composite (M-4) for the mixed gas of CO2 and CH4 was evaluated according to the method described above. In the pretreatment of the organic-inorganic hybrid membrane composite prior to the gas permeation and separation test, the flow rate of carbon dioxide supplied to the separation membrane module 25 was set to 74.7 sccm and the pressure was set to 0.1 MPaG.
[0307] The feed gas was a mixture of 74.7 sccm CO2 and 74.7 sccm CH4, and was fed at 0.30 MPaG. In other words, the CO2 concentration in the feed gas was 50.0%. The composition of the permeated gas was 88.2% CO2 and 11.8% CH4. The CO2 concentration in the passing gas was 47.8%.
[0308] The permeance of CO2 in the CO2 / CH4 mixed gas permeation of M-4, calculated from the permeation amount of each permeation gas and the composition of the feed gas and permeation gas, is 5.2E-07mol / (m 2 ·s·Pa)(=1600GPU) and the permeability coefficient was 16000 Barrer. The permeance of CH4 was 4.7E-08mol / (m 2 The separation factor α calculated from the permeance ratio was CO2 / CH4 The separation factor was 13. It was also shown that the separation of mixed gases exhibited good separation factor and permeability coefficient, and the performance exceeded the Robeson Upper Bound.
[0309] (Silicone resin film (M-5)) 5.4g of hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 1.04g of Silpot base agent were mixed with a stirrer until uniform, and then 0.10g of Silpot hardener was added and mixed well. 1.0g of the obtained mixture was dropped into a Teflon (registered trademark) petri dish with an inner diameter of 30 mm, and the Teflon (registered trademark) petri dish was placed in a vacuum dryer, and after hexane was volatilized, the temperature was raised to 80°C and held for 30 minutes. Then, the Teflon (registered trademark) petri dish was placed in a circulating thermostatic bath and held at 80°C for 5 hours to harden the matrix resin (P-1). The film was peeled off from the Teflon (registered trademark) petri dish to obtain a silicone resin film (M-5). The film thickness was 135 μm. The glass transition temperature of the silicone resin film (M-5) was measured using DSC according to the measurement method 1 of glass transition temperature by DSC, and was found to be -126°C.
[0310] The silicone resin membrane (M-5) had a CO2 permeability coefficient of 2500 Barrer and a CH4 permeability coefficient of 800 Barrer at 35°C. The silicone resin membrane (M-5) had a CO2 / CH4 separation coefficient of 3.1.
[0311] The weight average molecular weight of the Silpot base resin used in the preparation of M-5 was 28,000 in terms of polystyrene as measured according to GPC measurement method 1. The weight average molecular weight of the Silpot hardener used in the preparation of M-5 was 7,700 in terms of polystyrene as measured according to GPC measurement method 1.
[0312] (Silicone resin film (M-6)) 2.0 g of hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 0.63 g of poly(dimethylsiloxane), hydroxyl-terminated (18,000-22,000 cSt, manufactured by Sigma-Aldrich Japan) were mixed with a stirrer until uniform, and then 0.14 g of tetraethyl orthosilicate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.015 g of dibutyltin dilaurate (manufactured by Sigma-Aldrich Japan) were added and mixed well. The entire amount of the resulting mixture was dropped into a Teflon (registered trademark) petri dish with an inner diameter of 50 mm, the Teflon (registered trademark) petri dish was placed in a vacuum dryer, and after evaporating the hexane, the dish was left to stand overnight in a draft to harden the matrix resin (P-2). The film was peeled off from the Teflon (registered trademark) petri dish to obtain a silicone resin film (M-6). The film thickness was 159 μm.
[0313] The glass transition temperature of the silicone resin film (M-6) was measured according to the measurement method 2 for glass transition temperature by DSC and was found to be -124°C.
[0314] The silicone resin membrane (M-6) had a CO2 permeability coefficient of 4700 Barrer and a CH4 permeability coefficient of 1400 Barrer at 35°C. The silicone resin membrane (M-6) had a CO2 / CH4 separation coefficient of 3.3.
[0315] The weight average molecular weight of poly(dimethylsiloxane), hydroxy-terminated (18,000-22,000 cSt, manufactured by Sigma-Aldrich Japan) used in the preparation of M-6 was 74,000 in terms of polystyrene as measured by GPC measurement method 2.
[0316] (Organic-inorganic hybrid membrane composite (M-7)) The mixture was prepared in the same manner as M-4, except that the mixture was made of zeolite (Z-10 and Z-9), poly(dimethylsiloxane), hydroxyl-terminated (~750 cSt, Sigma-Aldrich Japan), hexane (Fujifilm Wako Pure Chemical Industries, Ltd.), tetraethyl orthosilicate (Tokyo Chemical Industry Co., Ltd.), and dibutyltin dilaurate (Sigma-Aldrich Japan) dried overnight at 120 °C, in a weight ratio of 26:10:40:3:0.7, and then stirred at room temperature for 330 minutes. The resulting mixture was used for membrane formation. A polyethersulfone membrane (hereinafter sometimes referred to as PES) immersed in desalted water (GVS Japan Co., Ltd.) was placed on a smooth plate, the water on the surface was removed, and the mixture was dropped onto the plate and applied using an applicator with a gap width of 2 mil. The solvent and water in the pores of the support layer were removed using a vacuum dryer to obtain an organic-inorganic hybrid membrane composite (M-7). The solid concentration of the mixed solution used for membrane formation was 47 mass%, and the zeolite content in the organic-inorganic hybrid membrane was 65.6 mass%. Among the zeolites, the content of zeolite (Z-10) was 3.5 times the content of zeolite (Z-9).
[0317] The cross section obtained by freeze-fracturing M-7 was observed with a scanning electron microscope, and the thickness of the organic-inorganic hybrid membrane, excluding the porous support layer from the organic-inorganic hybrid membrane composite (M-7), was measured. The thickness was 12 μm. The air permeability of the organic-inorganic hybrid membrane composite (M-7) was measured by the above-mentioned evaluation method, and was found to be 1.5 × 10 2 L / (m 2 ·h).
[0318] The CO2 permeability of the organic-inorganic hybrid membrane composite (M-7) at 35°C was 24,000 Barrer, the CH4 permeability was 13,000 Barrer, and the CO2 permeability was 1,990 GPU at 35°C. The CO2 / CH4 ideal separation factor was 19.
[0319] The average value of the occupation ratio of three fields of view calculated from the sum of the Si areas with brightness of 20 to 254 / the sum of the Si areas with brightness of 0 to 254, which is an index showing the penetration of the silicone resin into the porous support layer, was 23%.
[0320] The arithmetic mean roughness Ra of the organic-inorganic hybrid membrane composite surface divided by the film thickness of the separation-related layer (Ra (nm) / film thickness of separation-related layer (nm)) was 0.23.
[0321] The maximum continuous maximum length ratio of the inorganic filler was 98%. The average continuous maximum length ratio of the inorganic filler was 48%.
[0322] (Silicone resin film (M-8)) 2.0 g of hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 0.50 g of poly(dimethylsiloxane), hydroxyl-terminated (~750 cSt, manufactured by Sigma-Aldrich Japan) were mixed using a stirrer until uniform, and then 0.14 g of tetraethyl orthosilicate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.036 g of dibutyltin dilaurate (manufactured by Sigma-Aldrich Japan) were added and mixed well. The entire amount of the resulting mixture was dropped into a Teflon (registered trademark) petri dish with an inner diameter of 50 mm, the Teflon (registered trademark) petri dish was placed in a vacuum dryer, and after evaporating the hexane, the dish was left to stand overnight in a draft to harden the matrix resin (P-3). The film was peeled off from the Teflon (registered trademark) petri dish to obtain a silicone resin film (M-8). The film thickness was 89 μm. The glass transition temperature of the silicone resin film (M-8) was measured according to the measurement method 2 for glass transition temperature by DSC and was found to be -123°C.
[0323] The permeability coefficient of the silicone resin membrane (M-8) at 35°C for CO2 was 2500 Barrer, and for CH4 was 770 Barrer. The CO2 / CH4 separation coefficient of the silicone resin membrane (M-8) was 3.3.
[0324] The weight average molecular weight of poly(dimethylsiloxane), hydroxy-terminated (~750 cSt, Sigma-Aldrich Japan) used in the preparation of M-8 was 24,000 in terms of polystyrene, as measured by GPC measurement method 2.
[0325] As shown in Tables 1 to 3, it was shown that the organic-inorganic hybrid membrane composite with Ra (nm) / separation-related layer thickness (nm) of 0.050 or more exhibited excellent CO2 permeance. At this time, it was found that a certain level of selectivity was maintained and excellent performance was exhibited.
[0326] [Table 1]
[0327] [Table 2]
[0328] [Table 3] [Industrial Applicability]
[0329] The present invention can be used in any industrial field, but the organic-inorganic hybrid membrane composite, gas separation membrane module, and gas separation method of the present invention can be suitably used for CO2 separation and capture, such as removal of carbon dioxide from natural gas, CO2 capture from landfill gas, and CO2 capture (CO2, N2 mixture) from combustion exhaust gas from thermal power plants, etc., as well as hydrogen recovery and purification in various reaction processes in the oil refining industry and chemical industry, and production of oxygen-enriched gas, etc. [Explanation of symbols]
[0330] 1. Organic-inorganic hybrid membrane composite 2. Separation Membrane Module 3 Gas reservoir for keeping supply gas warm 4. Pressure gauge 5 Mass Flow Controller 6 Exhaust valve 7 Baratron Pressure Gauge 8 Gas reservoir for permeation gas 9 Liquid Nitrogen Trap 10 Vacuum Pump 11, 12, 13, 14, 15 valves 16 Temperature bath 17 Valve (hand valve) 18 Gas Cylinder 19 Gas chromatograph 20 Stream selection valve 21 Purge (exhaust gas) line 22 Exhaust valve 23 Mass Flow Meter 24, 28 Pressure gauge 25 Separation Membrane Module 26 Organic-inorganic hybrid membrane composite 27 Temperature bath 29, 30 Valve 31, 32 Mass flow controller 33, 34 Hand valve 35, 36 Gas cylinder
Claims
1. An organic-inorganic hybrid membrane composite having a porous support layer and a separation-related layer formed on the porous support layer, The separation-related layer comprises an organic-inorganic hybrid membrane, The organic-inorganic hybrid film is A matrix resin; and an inorganic filler having gas selectivity; the ratio of the arithmetic mean roughness of the surface of the organic-inorganic hybrid membrane composite to the film thickness of the separation-related layer is 0.050 or more; Organic-inorganic hybrid membrane composite.
2. the maximum value of the ratio of the maximum length of the continuous inorganic filler to the thickness of the separation-related layer of the organic-inorganic hybrid membrane composite is 20% or more; The organic-inorganic hybrid membrane composite according to claim 1 .
3. the inorganic filler has at least two peaks in particle size distribution and includes a first inorganic filler and a second inorganic filler having an average particle size smaller than that of the first inorganic filler; 2. The organic-inorganic hybrid membrane composite according to claim 1, wherein the first inorganic filler has an average particle size of 1 μm or more.
4. A method for performing at least one of gas separation and gas concentration, using the organic-inorganic hybrid membrane composite according to any one of claims 1 to 3.
5. A gas separation membrane module comprising the organic-inorganic hybrid membrane composite according to any one of claims 1 to 3.
6. A method for producing the organic-inorganic hybrid membrane composite according to any one of claims 1 to 3, a casting step of applying a dispersion liquid containing at least one of a precursor and an intermediate of a matrix resin and an inorganic filler having the gas selectivity onto the porous support layer; and a curing step of curing at least one of the precursor and the intermediate of the matrix resin to form the organic-inorganic hybrid film on the porous support layer. A method for producing an organic-inorganic hybrid membrane composite.